Lithium ion battery monomer, lithium ion battery and power utilization device
By using specific additives and pressure relief mechanism design in lithium-ion battery cells, the problem that existing lithium-ion batteries are difficult to take into account fast charging performance, cycle life and storage life is solved, and more efficient battery performance is achieved.
Patent Information
- Application Number
- CN202510009709.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-15
AI Technical Summary
Existing lithium-ion batteries are difficult to take into account fast charging performance, cycle life and storage life. In particular, the side reactions of carboxylate ester solvents in battery cells are severe, resulting in an increase in lithium ion consumption.
Using a lithium-ion battery cell containing lithium transition metal oxide, a carboxylic acid ester solvent and a first additive are added to the electrolyte. The reduction and decomposition potential of the first additive is between 1.45V and 2V to preferentially form an SEI film rich in inorganic components to reduce side reactions. At the same time, a pressure relief mechanism is provided in the housing, and the actuation pressure is between 0.5MPa and 1.8MPa to reduce the risk of pressure relief.
By optimizing the electrolyte composition and pressure relief mechanism design, lithium-ion battery cells can effectively reduce side reactions, extend cycle life and storage life, while maintaining fast charging performance.
Smart Images

Figure CN119833719A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of batteries, and more specifically, to a lithium-ion battery cell, a lithium-ion battery, and an electrical device. Background Art
[0002] With the increasing environmental pollution, the new energy industry has attracted more and more attention. In the new energy industry, battery technology is an important factor related to its development.
[0003] The development of battery technology needs to consider various design factors, such as energy density, cycle life, storage life, capacity, fast charging performance, reliability, etc. How to provide a lithium-ion battery cell with fast charging performance, long cycle life, and long storage life is a technical problem that亟待解决 (needs to be solved urgently). Summary of the Invention
[0004] The present application is made in view of the above problems, and its purpose is to provide a lithium-ion battery cell with fast charging performance, long cycle life, and long storage life.
[0005] To achieve the above purpose, the present application provides a lithium-ion battery cell, a lithium-ion battery, and an electrical device.
[0006] In a first aspect, a lithium-ion battery cell is provided, including: a positive electrode tab, the positive electrode tab includes a positive electrode film layer, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a lithium transition metal oxide; an electrolyte, the electrolyte includes a carboxylic ester solvent and a first additive, and the reduction decomposition potential V1 of the first additive satisfies: 1.45V < V1 ≤ 2V; a housing, the housing is used to accommodate the positive electrode tab and the electrolyte, the housing is provided with a pressure relief mechanism, and the actuation pressure P of the pressure relief mechanism satisfies: 0.5MPa ≤ P ≤ 1.8MPa.
[0007] In an embodiment of the present application, the positive electrode sheet includes a lithium transition metal oxide, the electrolyte includes a carboxylate solvent, and the lithium ion battery monomer has fast charging performance and a relatively high energy density; the reduction decomposition potential V1 of the first additive satisfies: 1.45V < V1 ≤ 2V, which is beneficial to improving the cycle life of the lithium ion battery monomer. The specific principle is speculated as follows: The first additive that satisfies the above reduction decomposition potential can form a SEI film rich in inorganic components on the negative electrode earlier than additives with other reduction decomposition potentials, which can reduce the contact between the negative electrode and the carboxylate solvent, reduce the side reactions of the carboxylate solvent at the negative electrode, and thus reduce the consumption of lithium ions, improving the cycle life of the lithium ion battery monomer. In addition, the housing is provided with a pressure relief mechanism, and the actuation pressure P of the pressure relief mechanism satisfies: 0.5MPa ≤ P ≤ 1.8MPa, which can reduce the risk of the pressure relief mechanism actuating and opening the valve during the normal use of the battery monomer, and is beneficial to improving the storage life of the lithium ion battery monomer. Therefore, the lithium ion battery monomer of the embodiment of the present application can take into account fast charging performance, cycle life and storage life.
[0008] In a possible implementation, 0.7MPa ≤ P ≤ 1.5MPa. In this way, it is beneficial to further improve the cycle life of the lithium ion battery monomer.
[0009] In a possible implementation, 0.8MPa ≤ P ≤ 1.4MPa. In this way, it is beneficial to further improve the cycle life of the lithium ion battery monomer.
[0010] In a possible implementation, the first additive includes one or more of fluorophosphate, borophosphate or vinylene sulfate.
[0011] When the first additive satisfies the above types and the reduction decomposition potential of the first additive is in the range of 1.45V to 2V, it is beneficial to reduce the risk of continuous side reactions of the carboxylate solvent at the negative electrode, and thus is beneficial to reducing the consumption of lithium ions and improving the cycle life of the lithium ion battery monomer. The specific principle is speculated as follows: The first additive can form a CEI film on the positive electrode, reducing the side reactions of the carboxylate solvent at the positive electrode, so that the products of the side reactions can be reduced from moving to the negative electrode to damage the SEI film at the negative electrode, which is beneficial to reducing the risk of continuous side reactions of the carboxylate solvent at the negative electrode; in addition, the reduction decomposition potential of the first additive is in the above range, and it can form a film on the negative electrode earlier than the carboxylate solvent, and the formed SEI film rich in inorganic components is relatively stable, which can reduce the risk of continuous side reactions of the carboxylate solvent at the negative electrode.
[0012] In a possible implementation, the first additive includes one or more of LiDFOP, 3DTD or LiDFOB.
[0013] The first additive helps to reduce the consumption of active lithium ions and increase the cycle life of lithium-ion battery cells.
[0014] In a possible implementation, based on the total mass of the electrolyte, the mass content of the first additive is less than or equal to 7wt%. This is conducive to forming a relatively dense and stable CEI and SEI film at the positive and negative electrodes, reducing the side reactions of carboxylic acid ester solvents, reducing the consumption of lithium ions, and improving the cycle life of lithium-ion battery cells. It can also reduce the increase in interface impedance caused by excessive mass content of the first additive, and the battery cell has a faster charging speed and a shorter charging time. In this way, the battery cell can take into account both cycle life and fast charging performance.
[0015] In a possible implementation, based on the total mass of the electrolyte, the mass content of the first additive is 1wt% to 5%. In this way, the lithium-ion battery cell can have both better fast charging performance and longer cycle life.
[0016] In a possible implementation, based on the total mass of the electrolyte, the mass content of the first additive is 0wt% to 4%, which is helpful to reduce the risk of more side reactions due to the poor thermal stability and chemical stability of the first additive itself, thereby reducing the adverse effects on the cycle life of the lithium-ion battery monomer.
[0017] In a possible implementation, based on the total mass of the electrolyte, the mass content of the first additive is 0.01wt% to 2.5%. In this way, the lithium-ion battery cell can have a higher cycle life.
[0018] In a possible implementation, the electrolyte further includes a second additive, and the reduction decomposition potential V2 of the second additive satisfies: 1.0V≤V1≤1.45V. The combination of the first additive and the second additive is beneficial to further improve the cycle life of the lithium-ion battery cell. The specific principle is speculated to be: the first additive and the second additive have different reduction decomposition potentials, which is beneficial to the gradient formation of the SEI film, that is, SEI films of different components can be formed at different stages of the charge and discharge cycle of the lithium-ion battery cell, so that the SEI film at the negative electrode is more dense and stable, which is beneficial to reduce the side reaction of the carboxylate solvent at the negative electrode and reduce the consumption of lithium ions.
[0019] In a possible implementation, the second additive includes one or more of a carbonate compound, a sulfonate compound, a vinyl sulfate compound, or a sultone compound.
[0020] When the second additive meets the above categories and the reduction decomposition potential of the second additive is within the range of 1.0V to 1.45V, it is beneficial to improve the cycle life of the lithium-ion battery monomer. The specific principle is speculated to be: the second additive helps to form an SEI film rich in organic components, and the SEI film rich in organic components has high toughness, which can reduce the risk of the SEI film rich in inorganic components formed by the first additive being brittle and ruptured during the later charging and discharging process, resulting in the continued side reaction of the carboxylic acid ester solvent at the negative electrode, thereby helping to reduce the consumption of lithium ions.
[0021] In a possible implementation, the second additive includes: one or more of MMDS, FEC, VC, DTD, 2DTD or PS. The second additive helps to further improve the cycle life of the battery cell. The specific mechanism is speculated to be: the second additive helps to form a CEI film at the positive electrode, which is beneficial to reduce the side reaction of the carboxylic acid ester solvent at the positive electrode and reduce the consumption of lithium ions.
[0022] In a possible implementation, the second additive includes: one or more of MMDS, FEC or PS. The second additive is not only conducive to improving the cycle life of the battery cell, but also conducive to reducing the gas generation in the battery cell, thereby helping to reduce the pressure in the battery cell and improve the storage life of the battery cell.
[0023] In a possible implementation, based on the total mass of the electrolyte, the mass content of the second additive is less than or equal to 12wt%. In this way, it is conducive to forming a denser and more stable SEI film and CEI film at the negative electrode or the positive electrode, reducing the side reaction of the carboxylic acid ester solvent, reducing the consumption of lithium ions, and improving the cycle life of the lithium-ion battery cell. It can also reduce the increase in interface impedance caused by excessive mass content of the second additive, and the battery cell has a faster charging speed and a shorter charging time. In this way, the battery cell can take into account both cycle life and fast charging performance.
[0024] In a possible implementation, based on the total mass of the electrolyte, the mass content of the second additive is 2 wt % to 9 wt %. In this way, the lithium-ion battery cell can have both better fast charging performance and longer cycle life.
[0025] In a possible implementation, based on the total mass of the electrolyte, the mass content of the second additive is 0wt% to 10wt%. This helps to reduce the risk of more side reactions due to the poor thermal and chemical stability of the second additive itself, thereby reducing the adverse effects on the cycle life of the lithium-ion battery monomer.
[0026] In a possible implementation, based on the total mass of the electrolyte, the mass content of the second additive is 0.01 wt % to 7 wt %. In this way, the lithium-ion battery cell can have a higher cycle life.
[0027] In a possible implementation, based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is less than or equal to 16wt%. In this way, it is beneficial to form a relatively dense and stable SEI film and CEI film at the negative electrode and the positive electrode, reduce the side reaction of the carboxylic acid ester solvent, reduce the consumption of lithium ions, and improve the cycle life of the lithium-ion battery cell. It can also reduce the increase in interface impedance caused by excessive mass contents of the first additive and the second additive, and the battery cell has a faster charging speed and a shorter charging time. In this way, the battery cell can take into account both cycle life and fast charging performance.
[0028] In a possible implementation, based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 3 wt % to 12 wt %. In this way, the lithium-ion battery cell can have both better fast charging performance and longer cycle life.
[0029] In a possible implementation, based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 0wt% to 14%. In this way, the remaining amount of the first additive and the second additive is small, which is conducive to reducing the risk of more side reactions due to the poor thermal stability and chemical stability of the first additive and / or the second additive itself, thereby reducing the adverse effects on the cycle life of the lithium-ion battery monomer.
[0030] In a possible implementation, based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 0.02wt% to 10%, which is beneficial to improving the cycle life of the lithium-ion battery cell.
[0031] In a possible implementation, the first additive includes 3DTD, and the second additive includes FEC. In this way, the battery cell has a longer cycle life.
[0032] In a possible implementation, based on the total mass of the electrolyte, the mass content of the first additive is 1wt% to 2wt%, and the mass content of the second additive is 1wt% to 2wt%. In this way, the first additive and the second additive have relatively suitable mass contents, and the battery cell has a longer cycle life and a shorter fast charging time.
[0033] In a possible implementation, the first additive includes 3DTD, LiDFOP and LiDFOB, and the second additive includes MMDS, FEC and PS.
[0034] In the first additive, the combination of 3DTD, LiDFOP and LiDFOB is beneficial to further improve the cycle life of the battery cell; in the second additive, MMDS, FEC and PS are beneficial to further improve the cycle life of the battery cell.
[0035] In a possible implementation, based on the total mass of the electrolyte, the mass content of the first additive is 2wt% to 4wt%, and the mass content of the second additive is 5wt% to 7wt%. In this way, the battery cell has a longer cycle life and a shorter fast charging time.
[0036] In a possible implementation, the positive electrode film layer further includes a conductive agent, and the conductive agent includes carbon nanotubes. In this way, the positive electrode plate has a smaller resistance, the temperature rise of the lithium-ion battery cell is smaller when the lithium-ion battery cell is charged at a high current rate, and fewer side reactions occur in the lithium-ion battery cell, which helps to improve the cycle life of the lithium-ion battery cell.
[0037] In a possible implementation, based on the total mass of the positive electrode film layer, the mass content A of the carbon nanotubes satisfies: 0.05wt%≤A≤1wt%. In this way, the carbon nanotubes have a suitable mass content, the temperature rise in the lithium-ion battery cell is less, the side reaction is less, the lithium ion consumption is less, and the cycle life of the lithium-ion battery cell is longer.
[0038] In a possible implementation, 0.05 wt%≤A≤0.5 wt%. In this way, the lithium-ion battery cell has a more suitable cycle life.
[0039] In a possible implementation, the conductive agent further includes carbon black, and based on the total mass of the positive electrode film layer, the mass content B of the carbon black satisfies: 0.1wt%≤B≤1wt%. In this way, the conductive agent includes carbon black and carbon nanotubes, and the carbon black and carbon nanotubes have appropriate mass contents, and the lithium-ion battery monomer can have a longer cycle life.
[0040] In a possible implementation, based on the total mass of the positive electrode film layer, the sum of the mass content of the carbon black and the carbon nanotubes is 0.05wt% to 2wt%. In this way, the carbon black and the carbon nanotubes have appropriate mass content, the positive electrode sheet has appropriate resistance, the temperature rise in the lithium-ion battery cell is less, the side reaction is less, and the lithium-ion battery cell can have a longer cycle life.
[0041] In a possible implementation, the carboxylate solvent includes one or more of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl acrylate or ethyl acrylate. By selecting the above carboxylate solvent, the electrolyte has a lower viscosity and a higher ionic conductivity, which is conducive to improving the fast charging performance of the lithium-ion battery monomer.
[0042] In a possible implementation, the carboxylate solvent includes: one or more of methyl acetate or ethyl acetate. The carboxylate solvent has a relatively low viscosity, which is beneficial to the diffusion and transmission of lithium ions, thereby improving the fast charging performance of the battery cell.
[0043] In a possible implementation, the ion conductivity of the electrolyte is 9 mS / cm to 23 mS / cm. The electrolyte has a high ion conductivity, which is conducive to the diffusion and transmission of lithium ions, and the lithium-ion battery cell has a better fast charging performance.
[0044] In a possible implementation, the ion conductivity of the electrolyte is 9 mS / cm to 18 mS / cm. In this way, the electrolyte has a higher ion conductivity, and the lithium-ion battery cell has a better fast charging performance.
[0045] In a possible implementation, the viscosity of the electrolyte is 1 mm 2 / s~3mm 2 / s. In this way, the electrolyte has a lower viscosity, which is conducive to the diffusion and transmission of lithium ions, and the lithium-ion battery monomer has better fast charging performance.
[0046] In a possible implementation, based on the total mass of the electrolyte, the mass content W3 of the carboxylic acid ester solvent satisfies: 5wt%≤W3≤80wt%.
[0047] When W3 is greater than or equal to 5wt%, the electrolyte has a lower viscosity, higher ion conductivity, and the lithium-ion battery cell has a better fast-charging performance; when W3 is less than or equal to 80wt%, the risk of excessive consumption of active lithium ions due to excessive carboxylate solvent can be reduced, which is beneficial to improving the cycle life of the lithium-ion battery cell. In this way, the battery cell can take into account both fast-charging performance and cycle life.
[0048] In a possible implementation, the carboxylic acid ester solvent includes methyl acetate, and based on the total mass of the electrolyte, the mass content W4 of the methyl acetate satisfies: 5wt%≤W4≤80wt%. Methyl acetate has high ionic conductivity and low viscosity. When the mass content of methyl acetate is within the range of 5wt% to 80wt%, the battery monomer can have good fast charging performance.
[0049] In a possible implementation, 15wt%≤W4≤30wt%. Methyl acetate has a suitable mass content, and the gas generation in the battery cell is less, and the battery cell has better comprehensive performance.
[0050] In a possible implementation, the carboxylate solvent includes ethyl acetate, and based on the total mass of the electrolyte, the mass content W5 of the carboxylate solvent satisfies: 5wt%≤W5≤80wt%.
[0051] Ethyl acetate has a more suitable ionic conductivity, and the gas produced by the side reaction of ethyl acetate is also less. By setting the mass content of ethyl acetate to 5wt% to 80wt%, the battery cell can have better fast charging performance, cycle performance, and less gas production.
[0052] In a possible implementation, 15wt%≤W5≤50wt%. In this way, the electrolyte can have a higher ion conductivity, and the battery cell can have a better fast charging performance.
[0053] In a possible implementation, the carboxylic acid ester solvent includes methyl acetate and ethyl acetate, and based on the total mass of the electrolyte, the mass content of methyl acetate is 5wt% to 80wt%, and the mass content of ethyl acetate is 5wt% to 80wt%. Ethyl acetate has a more suitable ionic conductivity and viscosity and less gas production, and methyl acetate has a higher ionic conductivity, a lower viscosity and a more suitable gas production. By matching ethyl acetate and methyl acetate, the fast charging performance and gas production of lithium-ion battery monomers can be balanced, and thus the fast charging performance and storage life of lithium-ion battery monomers can be taken into account.
[0054] In a possible implementation, the carboxylic acid ester solvent includes methyl acetate and ethyl acetate, and based on the total mass of the electrolyte, the mass content of methyl acetate is 15wt% to 30wt%, and the mass content of ethyl acetate is 25wt% to 50wt%. In this way, ethyl acetate and methyl acetate have appropriate mass contents, and the lithium-ion battery cell has good fast charging performance and less gas production, thereby reducing the adverse effects of excessive gas production on the interface of the battery cell (such as lithium deposition at the negative electrode) and reliability.
[0055] In a possible implementation, the lithium-ion battery cell further includes: a negative electrode plate, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based material or a silicon-based material.
[0056] In a possible implementation, the negative electrode active material includes a carbon-based material and a silicon-based material, and the mass content of silicon in the silicon-based material is 0.5wt% to 50wt% based on the total mass of the negative electrode active material. In this way, the negative electrode active material includes a silicon-based material, and the lithium-ion battery cell has a higher energy density; the mass content of the silicon element meets the above range, and the lithium-ion battery cell has a more suitable expansion rate, which can take into account both high energy density and high reliability. In addition, through the combination of silicon-based materials and the first additive and the second additive, the battery cell can take into account both high energy density and less volume expansion.
[0057] In a possible implementation, based on the total mass of the negative electrode active material, the mass content of silicon in the silicon-based material is 0.5 wt% to 10 wt%. In this way, the lithium-ion battery cell can have both high energy density and high reliability.
[0058] In a possible implementation, the carbon-based material includes a core portion and a second coating layer at least coated on the surface of the core portion, the core portion includes graphite, and the carbon-based material satisfies at least one of the following conditions: in the cumulative distribution curve of R values obtained by the carbon-based material in the surface scanning mode of a laser microscopy confocal Raman spectrometer, the R value R50 with a cumulative distribution of 50% is 0.15-0.50; in the R values obtained of the carbon-based material, the number of R values less than or equal to 0.11 accounts for less than or equal to 15%; in the cumulative distribution curve of R values obtained by the carbon-based material in the surface scanning mode of a laser microscopy confocal Raman spectrometer, the concentration of R values (R90-R10) / R50 is less than or equal to 2.3; among all the R values obtained by the carbon-based material, the number of R values R50 less than 50% of the cumulative distribution of the core portion accounts for less than or equal to 10%.
[0059] The provision of the second coating layer is helpful to reduce the side reaction between graphite and carboxylic acid ester solvents, thereby helping to reduce the consumption of lithium ions and improve the cycle life of lithium ion battery cells.
[0060] R50 can reflect the degree of surface defects of carbon-based materials. Setting R50 to 0.15-0.50 is conducive to reducing the degree of side reactions on the surface of carbon-based materials, reducing the consumption of lithium ions, and improving the cycle life of lithium-ion battery cells. It is also conducive to improving the charge exchange capacity of lithium ions in the electrolyte on the surface of carbon-based materials, so that the liquid phase transmission rate of lithium ions matches the solid phase transmission rate, and improving the fast charging capacity of lithium-ion battery cells. In addition, it is also conducive to using a lower content of the first additive and / or the second additive to improve the cycle life and fast charging capacity of the battery cell.
[0061] The cumulative distribution of the core graphite is 50% of the R value R50 generally does not exceed 0.11. Therefore, among all the R values of the obtained carbon-based materials, the proportion of the number of R values less than or equal to 0.11 can be used to indicate the degree of uncoating of the carbon-based material. The smaller the value, the smaller the degree of uncoating of the carbon-based material, which is conducive to reducing the side reactions of graphite and carboxylic acid ester solvents and the co-embedding phenomenon of electrolyte solvents during the cycle, and the lithium-ion battery monomer has good cycle performance; in addition, the smaller the degree of uncoating of the carbon-based material, the higher the surface coating degree of the carbon-based material, the isotropy of ion embedding, the charge exchange capacity of ions on the surface of the carbon-based material, and then the solid-liquid transmission rate of lithium ions is increased, which can match with the electrolyte and improve the fast charging capacity of the lithium-ion battery monomer. In addition, the smaller the degree of uncoating of the carbon-based material, the more uniform the SEI film is formed on the surface of the carbon-based material, which is conducive to reducing the adverse effects of the uneven SEI film on the cycle life.
[0062] The concentration of the R value can reflect the consistency of the second coating layer. By setting the concentration of the R value (R90-R10) / R50 to be less than or equal to 2.3, the second coating layer has better consistency, which is beneficial to reduce the side reaction between graphite and carboxylic acid ester solvents, and the lithium-ion battery monomer has a longer cycle life. In addition, the better the consistency of the second coating layer, the better the consistency of the SEI film formed on the surface of the carbon-based material, which is beneficial to improve the cycle life of the lithium-ion battery monomer.
[0063] Among all the R values obtained by the carbon-based material, the proportion of the number of R values R50 less than 50% of the cumulative distribution of the core portion can reflect the degree of non-coating of the carbon-based material. The smaller the value, the smaller the degree of non-coating of the carbon-based material, which is beneficial to improving the cycle performance of the lithium-ion battery monomer. By setting the proportion of the number of R values R50 less than 50% of the cumulative distribution of the core portion in all the R values obtained by the carbon-based material to be less than or equal to 10%, the lithium-ion battery monomer has a higher cycle life.
[0064] In a possible implementation, the carbon-based material satisfies at least one of the following conditions: in the cumulative distribution curve of R values obtained by the carbon-based material in the surface scanning mode of a laser micro-confocal Raman spectrometer, the R value R50 with a cumulative distribution of 50% is 0.15-0.30; among the R values obtained for the carbon-based material, the number of R values less than or equal to 0.11 accounts for less than or equal to 10%; in the cumulative distribution curve of R values obtained by the carbon-based material in the surface scanning mode of a laser micro-confocal Raman spectrometer, the concentration of R values (R90-R10) / R50 is less than or equal to 1.7; among all the R values obtained for the carbon-based material, the number of R values R50 with a cumulative distribution less than 50% of the core portion accounts for less than or equal to 6%. In this way, the surface disorder of the carbon-based material is within the above range and the degree of coating is high, which is beneficial to reduce the degree of side reactions on the surface of the carbon-based material and the co-embedding phenomenon of the electrolyte solvent during the cycle, and the lithium-ion battery monomer has good cycle performance; in addition, when (R90-R10) / R50 is less than or equal to 1.7, it is beneficial to further improve the cycle life; among all the R values obtained by the carbon-based material, when the number of R values R50 less than 50% of the cumulative distribution of the core is less than or equal to 6%, it is beneficial to further improve the cycle life.
[0065] In a possible implementation, in the R value cumulative distribution curve obtained by the carbon-based material in the surface scanning mode of the laser microscopic confocal Raman spectrometer, the R value R50 with a cumulative distribution of 50% is 0.15-0.30. In this way, the surface disorder of the carbon-based material is within the above range, which is conducive to reducing the degree of side reactions on the surface of the carbon-based material, and the lithium-ion battery monomer has good cycle performance.
[0066] In a possible implementation, among the R values of the obtained carbon-based materials, the number of R values less than or equal to 0.11 accounts for less than or equal to 6%. In this way, the carbon-based material has a high degree of coating, which is conducive to reducing the degree of side reactions on the surface of the carbon-based material and the co-embedding phenomenon of the electrolyte solvent during the cycle, and the lithium-ion battery monomer has good cycle performance.
[0067] In one possible implementation, the air oxidation temperature T0 of the carbon-based material is 630°C to 730°C, wherein the air oxidation temperature T0 is the temperature corresponding to the intersection of two tangents at two points corresponding to 500°C and T1 temperatures on the thermogravimetric curve of the carbon-based material, respectively, and the T1 temperature is the peak temperature of the maximum area peak in the differential thermogravimetric curve of the carbon-based material. The thermogravimetric curve and the differential thermogravimetric curve can be obtained by thermogravimetric analysis under the following conditions: sample mass 10±0.05 mg, purge gas is air and the airflow rate is 60 mL / min, the heating rate is 5°C / min, and the test temperature range is 35°C to 950°C.
[0068] The negative electrode active material with an air oxidation temperature T0 of 630°C to 730°C has an appropriate number of surface defects, which makes the degree of side reactions of the battery cell within a controllable range. At the same time, it can also provide sufficient end surfaces for the embedding of active ions and match the lithium ion transfer rate of the electrolyte. Therefore, the battery cell can have improved fast charging performance while maintaining the cycle life.
[0069] In a possible implementation, the carbon-based material includes secondary particles formed by agglomeration of primary particles, and the volume average particle size of the carbon-based material is 8 μm to 18 μm.
[0070] On the one hand, the carbon-based materials with a volume average particle size within the above range can make use of a certain number of primary particles in the secondary particles to make the carbon-based materials have a suitable embedding surface, and the solid-phase transmission rate and solid-liquid transmission rate of active ions in the carbon-based materials can match the liquid-phase transmission rate of lithium ions in the electrolyte, thereby improving the fast charging performance of the battery; on the other hand, it can also have the advantages of high compaction density and large capacity of secondary particles, thereby improving the fast charging performance of the battery while taking into account the energy density of the battery cell.
[0071] In a possible implementation, the carbon-based material includes unagglomerated primary particles, and the volume average particle size of the carbon-based material is 5 μm to 13 μm.
[0072] Carbon-based materials with a volume average particle size within the above range have higher interface stability than particles with smaller particle sizes, which helps to reduce the extent of side reactions in battery cells and improve the cycle life of battery cells.
[0073] In a possible implementation manner, the core portion of the carbon-based material includes artificial graphite, and the second coating layer includes amorphous carbon.
[0074] Artificial graphite has fewer defects and higher capacity, which can reduce the degree of side reactions with electrolytes, give full play to the high capacity of graphite, reduce gas production, and make the battery cells have both high energy density and good cycle performance. Amorphous carbon has higher hardness, so it also has good compressive resistance, has a stronger ability to maintain the pore structure of the negative electrode film during the cycle, and has better electrolyte wettability of the negative electrode sheet, so it is also beneficial to improve the cycle performance of the battery cells.
[0075] In a possible implementation, the surface density of the negative electrode sheet on one side is 0.05 mg / mm 2 ~0.11mg / mm 2 , and / or, the compaction density of the negative electrode sheet is 1.2 g / cm 3~ 1.7g / cm 3By combining the carboxylic acid ester solvent of the present application with the surface density and the compaction density, the lithium-ion battery monomer can have a better fast charging performance while having a larger surface density and compaction density.
[0076] In a possible implementation, the lithium transition metal oxide includes lithium nickel cobalt manganese oxide.
[0077] In a possible implementation, the lithium transition metal oxide includes unagglomerated primary particles. In this way, the degree of side reaction between the lithium transition metal oxide and the carboxylic acid ester solvent is low, which is conducive to further improving the cycle life of the lithium ion battery monomer.
[0078] In a possible implementation, the volume average particle size Dv50 of the lithium transition metal oxide is 2 μm to 5 μm. The lithium transition metal oxide within the above particle size range has a low degree of side reaction with carboxylic acid ester solvents, which is conducive to further improving the cycle life of lithium ion battery monomers.
[0079] In one possible implementation, the lithium transition metal oxide satisfies at least one of the following conditions: based on the total moles of transition metals in the lithium transition metal oxide, the molar content of cobalt is less than or equal to 20%; based on the total moles of transition metals in the lithium transition metal oxide, the molar content of nickel is less than 80%. The above arrangement is conducive to taking into account the gram capacity, kinetic performance and cost of lithium transition metal oxides, and thus to taking into account the energy density and fast charging performance of lithium-ion battery cells. In addition, setting the molar content of nickel to meet the above range is conducive to reducing the probability of nickel dissolution of lithium transition metal oxides under high voltage, and the combination with unagglomerated primary particles is also conducive to reducing the degree of side reactions between lithium transition metal oxides and carboxylic acid ester solvents, and improving the cycle performance of lithium-ion battery cells.
[0080] In one possible implementation, the lithium transition metal oxide satisfies at least one of the following conditions: based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of cobalt accounts for 5% to 12%; based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of nickel accounts for 65% to 70%. The above-mentioned setting is conducive to taking into account the gram capacity, kinetic performance and cost of lithium transition metal oxides, and thus is conducive to taking into account the cycle life and fast charging performance of lithium-ion battery cells. In addition, setting the molar content of nickel to meet the above range is also conducive to reducing the degree of side reactions between lithium transition metal oxides and carboxylic acid ester solvents, and improving the cycle performance of lithium-ion battery cells.
[0081] In one possible implementation, the lithium transition metal oxide includes secondary particles formed by agglomeration of primary particles, and the lithium transition metal oxide satisfies at least one of the following conditions: the volume average particle size Dv50 of the lithium transition metal oxide is 6 μm to 15 μm; the average particle size Dv50 of the primary particles in the secondary particles is 0.1 μm to 1.5 μm; based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of nickel is greater than or equal to 80%.
[0082] Forming high-nickel materials into large-sized secondary particles is beneficial to simultaneously increase the specific capacity of lithium transition metal oxides and improve the energy density of lithium-ion battery cells. At the same time, secondary particles are composed of small-diameter primary particles, which can shorten the transmission distance of lithium ions, increase the number of embedded end faces, reduce the DC impedance of battery cells, and improve the fast charging performance of battery cells.
[0083] In one possible implementation, in the lithium transition metal oxide particles, the mass proportion of the cobalt element near the surface of the particle is greater than the mass proportion of the cobalt element near the center of the particle, wherein the area near the surface of the particle is a region from the surface of the particle to a depth of 200 nm in the direction toward the geometric center of the particle, and the area near the center of the particle is a spherical region with a diameter of 200 nm and the geometric center of the particle cross section as the center of the circle.
[0084] The relatively high cobalt content on the surface of lithium transition metal oxides helps to improve the ionic conductivity of lithium transition metal oxides, improve the problem of lithium over-desorption on the surface of lithium transition metal oxides during charging and discharging, inhibit and reduce the cation mixing of the Li layer and the transition metal layer, stabilize the layered structure of lithium transition metal oxides, and reduce the risk of structural phase change on the surface of lithium transition metal oxides, thereby reducing the degree of side reactions of battery cells and improving the cycle life of battery cells. The relatively low cobalt content in the center of lithium transition metal oxides can simultaneously reduce the cost of lithium transition metal oxides.
[0085] In a possible implementation, the ratio of the mass proportion of the cobalt element near the surface of the particle to the mass proportion of the cobalt element near the center of the particle is 1.01 to 5. This helps to stabilize the layered structure of the lithium transition metal oxide and reduce the risk of structural phase change on the surface of the lithium transition metal oxide, thereby reducing the degree of side reactions of the battery monomer and improving the cycle life of the battery monomer.
[0086] In a possible implementation, the lithium transition metal oxide includes a substrate and a first coating layer that covers at least a portion of the surface of the substrate, and the first coating layer includes at least one of V, Mo, Ti, Al, or O. The provision of the first coating layer is conducive to reducing the side reaction of the carboxylic acid ester solvent at the positive electrode, reducing the consumption of lithium ions, and improving the cycle life of the lithium ion battery monomer.
[0087] In a possible implementation, the positive electrode active material further includes lithium-containing phosphate. Compared with a lithium-ion battery cell including only lithium transition metal oxide, a lithium-ion battery cell including lithium-containing phosphate and lithium transition metal oxide has a smaller impedance, which is conducive to improving the power of the lithium-ion battery cell.
[0088] In a possible implementation, based on the total mass of the positive electrode active material, the mass content of the lithium-containing phosphate is 1wt% to 50wt%. In this way, the lithium-containing phosphate and the lithium transition metal oxide both have relatively suitable mass contents, which can take into account the energy density, cycle performance and power of the lithium-ion battery monomer, and the lithium-ion battery monomer has good comprehensive performance.
[0089] In a possible implementation, based on the total mass of the positive electrode active material, the mass content of the lithium-containing phosphate is 1wt% to 5wt%. In this way, the energy density, cycle performance and power of the lithium-ion battery cell can be well balanced, and the lithium-ion battery cell has good comprehensive performance.
[0090] In a possible implementation, the lithium-containing phosphate includes at least one of lithium iron phosphate, lithium manganese phosphate or lithium manganese iron phosphate.
[0091] In a possible implementation, the single-side density of the positive electrode sheet is 0.09 mg / mm 2 ~0.15mg / mm 2 , and / or, the compaction density of the positive electrode sheet is 2.0g / cm3 to 3.8g / cm 3 When the surface density and compaction density of the positive electrode are large, the diffusion of lithium ions is affected to a certain extent, and the improvement of the fast charging performance of the lithium-ion battery monomer is small. By combining the carboxylic acid ester solvent of the present application with the surface density and compaction density, the lithium-ion battery monomer can have better fast charging performance with a large surface density and compaction density.
[0092] In a possible implementation manner, the material of the shell includes steel, and the thickness of the shell is 0.1 mm to 0.5 mm.
[0093] In a possible implementation, the thickness of the shell is 0.2 mm to 0.3 mm.
[0094] Steel has high strength. By setting the material of the shell to include steel, the pressure relief mechanism has a suitable actuation pressure, which is beneficial to improving the storage life of the lithium-ion battery cell.
[0095] In a possible implementation manner, the material of the shell includes aluminum, and the thickness of the shell is 0.3 mm to 1.0 mm.
[0096] In a possible implementation, the thickness of the shell is 0.5 mm to 0.6 mm.
[0097] Aluminum has high strength and relatively suitable processing performance. By setting the material of the shell to include aluminum, it is convenient to prepare the shell, and the pressure relief mechanism also has a suitable actuation pressure, which is beneficial to improving the storage life of the lithium-ion battery cell.
[0098] In a possible implementation, the electrolyte further includes a carbonate solvent, and the carbonate solvent includes one or more of ethylene carbonate, dimethyl carbonate, propylene carbonate or ethyl methyl carbonate. Carbonate solvents have lower viscosity, higher dielectric constant and good electrochemical stability. Lower viscosity is conducive to the rapid migration of lithium ions in the electrolyte, improving the fast charging performance of lithium-ion battery cells; higher dielectric constant is conducive to improving the solubility of lithium salts in the electrolyte, thereby helping to increase the concentration of lithium salts in the electrolyte; good electrochemical stability helps to increase the operating voltage range of lithium-ion battery cells, thereby increasing the capacity of lithium-ion battery cells. The combination of carbonate solvents and carboxylate solvents helps to improve the fast charging performance and cycle performance of lithium-ion battery cells.
[0099] In a possible implementation, the electrolyte further includes an electrolyte salt, and the electrolyte salt includes one or more of LiPF6 or LiFSI.
[0100] In a possible implementation, the electrolyte salt includes LiPF6 and LiFSI, and the mass content of LiFSI is 2 wt% to 30 wt% based on the total mass of the electrolyte salt.
[0101] LiFSI helps to form a LiF-rich SEI film, which can reduce the side reactions of carboxylate solvents at the negative electrode and improve the cycle life of lithium-ion battery cells.
[0102] In a possible implementation, the time t for charging the lithium-ion battery cell from 10% SOC to 80% SOC satisfies: t≤15 min. The lithium-ion battery cell has a shorter charging time and thus has a better fast charging performance.
[0103] In a possible implementation, t≤10 min. In this way, the lithium-ion battery cell has a shorter charging time and thus has better fast charging performance.
[0104] In a second aspect, a lithium-ion battery is provided, comprising the lithium-ion battery cell in the first aspect and any possible implementation manner thereof.
[0105] In a third aspect, an electrical device is provided, comprising the lithium-ion battery described in the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0106] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0107] Figure 1 A schematic diagram of a positive electrode sheet according to an embodiment of the present application;
[0108] Figure 2 A schematic diagram of a lithium-ion battery cell according to an embodiment of the present application;
[0109] Figure 3 A schematic diagram of a method for preparing a lithium-ion battery cell according to an embodiment of the present application;
[0110] Figure 4 A schematic diagram of a lithium-ion battery according to an embodiment of the present application;
[0111] Figure 5 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application.
[0112] Figure numerals: 1: positive electrode plate; 10: positive electrode current collector; 11: positive electrode film layer; 3: lithium-ion battery cell; 30: outer shell; 31: shell; 313: pressure relief mechanism; 32: end cover; 322: electrode terminal; 33: electrode assembly; 331: pole ear; 34: connecting member; 5: lithium-ion battery; 6: electrical device. DETAILED DESCRIPTION
[0113] The embodiments of the lithium-ion battery cell, lithium-ion battery, and electrical device of the present application are described in detail with appropriate reference to the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually the same structure may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0114] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0115] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0116] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0117] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0118] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0119] Unless otherwise specified, the following terms have the following meanings. Any undefined terms have their generally accepted meanings in the art.
[0120] Where mentioned, "reduction potential" refers to the electrode potential of a substance relative to a standard electrode. Specifically, the reduction potential is the electrode potential of the substance measured by placing the substance in a galvanic cell with a standard electrode. For example, in a lithium-ion battery, the standard electrode can be a lithium electrode.
[0121] Where mentioned, "reductive decomposition potential" refers to the electrode potential of a substance relative to a standard electrode when it decomposes.
[0122] The "actuation" mentioned in this application means that the pressure relief mechanism is in action or activated to a certain state, so that the internal pressure and temperature of the battery cell can be released. The action produced by the pressure relief mechanism may include but is not limited to: the components in the pressure relief mechanism move to form an exhaust channel, at least a part of the pressure relief mechanism ruptures, breaks, is torn or opened, and so on. When the pressure relief mechanism is actuated, the high-temperature and high-pressure substances inside the battery cell will be discharged from the actuated part as emissions. In this way, the battery cell can be depressurized and cooled under controllable pressure or temperature, thereby avoiding potential more serious accidents. Emissions include but are not limited to: electrolyte, dissolved or split positive and negative pole pieces, fragments of separators, high-temperature and high-pressure gases produced by the reaction, flames, and so on.
[0123] The “actuation pressure” mentioned in this application refers to the internal pressure of the battery cell when the pressure relief mechanism is actuated.
[0124] Next, embodiments of the present application are introduced.
[0125] The development of battery technology must consider many design factors at the same time, such as energy density, cycle life, discharge capacity, fast charging performance, reliability, etc. Carboxylate solvents have the characteristics of low viscosity and high ionic conductivity. Their application in electrolytes is conducive to improving the fast charging performance of lithium-ion battery cells. However, the side reactions of carboxylate solvents in lithium-ion battery cells are relatively violent, especially when carboxylate solvents are applied to battery cells including lithium transition metal oxides. Since the upper limit voltage of lithium transition metal oxides is higher, the amount of lithium desorption is larger, the structure of lithium transition metal oxides is unstable and it is easier to release oxygen, the side reactions of carboxylate solvents in the battery cells of this system are more violent, and the products generated by the side reactions destroy the SEI film at the negative electrode, resulting in a more violent reaction between the negative electrode and the carboxylate solvent, a large consumption of lithium ions, and it is difficult for the battery cells to take into account both fast charging performance and long cycle life. At the same time, the violent side reactions of carboxylate solvents with lithium transition metal oxides and negative electrode active materials at the negative electrode will lead to a large amount of gas production inside the lithium-ion battery cell, resulting in a large pressure inside the battery cell.
[0126] In view of this, the present application provides a lithium-ion battery cell including a lithium transition metal oxide. In the lithium-ion battery cell, the electrolyte includes a carboxylate solvent and a first additive, and the reduction decomposition potential V1 of the first additive satisfies: 1.45V < V1 ≤ 2V. The first additive has a higher reduction decomposition potential compared to other additives and can preferentially form a SEI film rich in inorganic components on the negative electrode, which helps to reduce the contact between the negative electrode and the carboxylate solvent, reduce the side reactions of the carboxylate solvent at the negative electrode, thereby reducing the consumption of lithium ions and improving the cycle life of the battery cell. In addition, a pressure relief mechanism is provided in the outer casing of the lithium-ion battery cell, and the actuation pressure of the pressure relief mechanism is 0.5MPa to 1.8MPa, which can reduce the risk of the pressure relief mechanism actuating and opening the valve during the normal use of the battery cell, and can also reduce the risk of emissions discharging from positions other than the pressure relief mechanism when the pressure relief mechanism actuates. Therefore, by adopting specific additives and controlling the actuation pressure of the pressure relief mechanism, while controlling the side reactions and gas generation in the battery cell, combined with the structural design, the air pressure bearing capacity of the battery cell is ensured, so that the lithium-ion battery cell can take into account the fast charging performance, cycle life and storage life.
[0127] During the charging process of the lithium-ion battery cell, lithium ions are removed from the positive electrode active material, move and embed into the negative electrode; during the discharging process, lithium ions are removed from the negative electrode, move and embed into the positive electrode active material.
[0128] It should be understood that the "embedding" process described in the present application refers to the process in which lithium ions are embedded in the positive electrode active material or the negative electrode due to an electrochemical reaction, and the "removal" and "deintercalation" processes described in the present application refer to the process in which lithium ions are removed from the positive electrode active material or the negative electrode due to an electrochemical reaction.
[0129] It should be understood that the reduction decomposition potential of the additive mentioned in the embodiments of the present application is the potential relative to the same standard electrode. As an example, the reduction decomposition potential of the additive is the reduction potential of the additive relative to the lithium electrode.
[0130] Generally, a lithium-ion battery cell includes a positive electrode plate, a negative electrode plate, an electrolyte and a separator. Next, the lithium-ion battery cell provided by the present application and each part in the lithium-ion battery cell will be introduced.
[0131] [Lithium-ion battery cell]
[0132] Figure 1 is a schematic diagram of the positive electrode plate of an embodiment of the present application. Figure 2 is a schematic diagram of a lithium-ion battery cell of an embodiment of the present application. The embodiments of the present application provide a lithium-ion battery cell. For example, in combination with Figure 1 and Figure 2As shown, the lithium-ion battery cell 3 includes a positive electrode plate 1 , an electrolyte and a housing 30 .
[0133] For example, Figure 1 As shown, the positive electrode sheet 1 includes a positive electrode current collector 10 and a positive electrode film layer 11 disposed on at least one side surface of the positive electrode current collector 10 .
[0134] Along the thickness direction of the positive electrode sheet 1, for example Figure 1 In the z direction, the positive electrode film layer 11 may be disposed on only one side surface of the positive electrode current collector 10 , or may be disposed on both side surfaces of the positive electrode current collector 10 .
[0135] The positive electrode film layer 11 includes a positive electrode active material, and the positive electrode active material includes a lithium transition metal oxide.
[0136] Lithium transition metal oxide refers to a class of oxides including lithium and transition metal elements. Structurally, it includes ternary materials with layered structures, such as LiCoO2, LiNiO2, etc., and also includes LiMn2O4 with spinel structure, etc. Ternary materials refer to lithium transition metal oxides including three different transition metal elements. It should be understood that ternary materials can also be doped with trace amounts of other transition metal elements, and it is generally believed that ternary materials doped with other transition metal elements are still ternary materials.
[0137] The electrolyte includes a carboxylic acid ester solvent and a first additive, and the reduction decomposition potential V1 of the first additive satisfies: 1.45V <V1≤2V。
[0138] Carboxylate solvents have lower viscosity and higher ionic conductivity. Including carboxylate solvents in the electrolyte is beneficial to the transmission and diffusion of lithium ions, thereby helping to improve the fast charging performance of lithium-ion battery cells.
[0139] The carboxylate solvent may be a solvent comprising a linear carboxylate. As an example, the carboxylate solvent comprises a compound having a structure shown in Formula I,
[0140]
[0141] Wherein, R1 and R2 each independently include at least one of a C1-C5 alkyl group and a C1-C5 halogenated alkyl group.
[0142] Specifically, as an example, the carboxylate solvent includes one or more of methyl formate (MF), methyl acetate (MA), and ethyl acetate (EA).
[0143] The reduction decomposition potential of the first additive may be 1.48 V, 1.5 V, 1.6 V, 1.8 V, 1.9 V, 2 V, or any value within the above range.
[0144] The first additive is beneficial to improving the cycle life of lithium-ion battery cells. The principle is speculated to be: the reduction decomposition potential of the first additive is 1.45V to 2V, and the first additive that meets the above requirements can prioritize other additives with reduction decomposition potentials to generate a solid electrolyte interface (SEI) film rich in inorganic components at the negative electrode, blocking the contact between the carboxylic acid ester solvent and the negative electrode, reducing the side reactions of the carboxylic acid ester solvent, thereby reducing the consumption of lithium ions and improving the cycle life of lithium-ion battery cells.
[0145] The housing 30 is provided with a pressure relief mechanism 313 , and an actuation pressure P of the pressure relief mechanism 313 satisfies: 0.5 MPa≤P≤1.8 MPa.
[0146] The pressure relief mechanism 313 can be disposed on any wall of the housing 30. The housing 30 includes a shell 31 and an end cover 32. The shell 31 has an opening, and the end cover 32 covers the opening to form a space for accommodating electrolyte. As an example, the pressure relief mechanism 313 is disposed on the end cover 32; as another example, the pressure relief mechanism 313 is disposed on any wall of the housing 31.
[0147] The pressure relief mechanism 313 is used to discharge substances in the lithium-ion battery cell 3, such as byproducts generated by reactions in the lithium-ion battery cell (such as gases or solids generated by reactions), fragments of positive electrode sheets, fragments of separators, fragments of negative electrode sheets, etc.
[0148] As an example, when the internal pressure of the lithium-ion battery cell 3 reaches a predetermined threshold, it is actuated to release the internal pressure or temperature. When the internal pressure of the lithium-ion battery cell 3 reaches a predetermined threshold, the pressure relief mechanism 313 performs an action or a weak structure provided in the pressure relief mechanism 313 is destroyed, thereby forming an opening or channel for internal pressure relief. The threshold design varies according to different design requirements. The threshold may depend on one or more materials of the positive electrode plate, the negative electrode plate, the electrolyte and the separator in the lithium-ion battery cell.
[0149] As an example, the pressure relief mechanism 313 may be integrally formed with the housing 30 .
[0150] As an example, the pressure relief mechanism 313 may also be separately provided and connected to the housing 30 .
[0151] The actuation pressure of the pressure relief mechanism 313 is the internal pressure of the lithium-ion battery cell 3 when the pressure relief mechanism 313 is actuated.
[0152] The actuation pressure of the pressure relief mechanism 313 can be adjusted by changing the materials of the housing and the pressure relief mechanism, and the thickness of the housing where the pressure relief mechanism 313 is provided.
[0153] The actuating pressure P of the pressure relief mechanism 313 may be 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa, 1.5 MPa, 1.6 MPa, 1.7 MPa, 1.8 MPa or any value within the above range.
[0154] When the internal pressure of the lithium-ion battery cell 3 reaches the actuation pressure of the pressure relief mechanism 313, the pressure relief mechanism 313 is actuated. Due to the addition of carboxylic acid ester solvents, the gas production in the lithium-ion battery cell 3 increases, and the internal pressure in the lithium-ion battery cell 3 also increases. By setting the actuation pressure of the pressure relief mechanism 313 to be greater than or equal to 0.5MPa, the risk of the pressure increase in the lithium-ion battery cell caused by the addition of carboxylic acid ester solvents, which in turn causes the pressure relief mechanism 313 to be actuated and opened in advance, can be reduced, which is beneficial to improving the storage life of the lithium-ion battery cell 3; setting the actuation pressure of the pressure relief mechanism 313 to be less than or equal to 1.8Mpa can reduce the risk of the discharge of the lithium-ion battery cell from a position outside the pressure relief mechanism 313 when the lithium-ion battery cell has thermal runaway, which is beneficial to improving the reliability of the lithium-ion battery cell.
[0155] In some embodiments, 0.7 MPa≤P≤1.5 MPa.
[0156] When the actuation pressure of the pressure relief mechanism 313 is 0.7 MPa to 1.5 MPa, it is beneficial to further reduce the risk of the pressure relief mechanism 313 actuating the valve to open during normal use of the lithium-ion battery cell, and is beneficial to increase the storage time and storage life of the lithium-ion battery cell.
[0157] In some embodiments, the actuation pressure of the pressure relief mechanism 313 is 0.8 MPa to 1.4 MPa. This is helpful to increase the storage time and storage life of the lithium-ion battery cells.
[0158] In some embodiments, the first additive includes one or more of fluorophosphates, borophosphates, or vinyl sulfates.
[0159] The fluorophosphate includes one or more of monofluorophosphate and difluorophosphate. As an example, the fluorophosphate includes lithium bis(oxalato)difluorophosphate (LiDFOP).
[0160] The borophosphate includes at least one of tetrafluoroborate, bisoxalatoborate, and fluorine-containing oxalatoborate. As an example, the borate includes lithium difluorooxalatoborate (LiDFOB).
[0161] As an example, the vinyl sulfate includes vinyl trisulfate (3DTD).
[0162] The above-mentioned type of first additive is conducive to reducing the risk of carboxylate solvents continuously undergoing side reactions at the negative electrode, thereby helping to reduce the consumption of lithium ions and increase the cycle life of lithium-ion battery cells. The specific principle is speculated to be: the first additive can form an electrochemical interface (CEI) film at the positive electrode, reducing the side reactions of carboxylate solvents at the positive electrode, thereby reducing the damage to the SEI film at the negative electrode caused by the products of the side reactions moving to the negative electrode, which is conducive to reducing the risk of carboxylate solvents continuously undergoing side reactions at the negative electrode; in addition, the reduction decomposition potential of the first additive is in the range of 1.45V to 2V, which can form a film at the negative electrode earlier than the carboxylate solvents, and the formed SEI film rich in inorganic components is relatively stable, which can reduce the risk of carboxylate solvents continuously undergoing side reactions at the negative electrode.
[0163] In some embodiments, the first additive includes one or more of lithium bis(oxalatodifluorophosphate) (LiDFOP), ethylene trisulfate (3DTD), or lithium difluorooxalatoborate (LiDFOB).
[0164] Among them, the structural formula of 3DTD is
[0165] 3DTD, LiDFOP and LiDFOB are beneficial to the cycle life of lithium-ion battery cells. The principle is speculated to be: the above additives help to form a network structure of CEI film and SEI film on the positive electrode side and the negative electrode side, so that the CEI film and SEI film are more compact and stable, which helps to inhibit the side reactions of the electrolyte at the positive and negative electrodes in different cycle stages of the lithium-ion battery cells, thereby improving the cycle life of the lithium-ion battery cells; and / or, the above additives help to stabilize the positive electrode active material, further reduce the side reactions at the positive electrode, thereby reducing the consumption of lithium ions and improving the cycle life of the battery cells.
[0166] In addition, 3DTD is beneficial to the improvement of fast charging performance. The principle is speculated to be: the CEI film and SEI film formed by 3DTD have a smaller increase in the impedance of the battery cell, and the battery cell can have better fast charging performance.
[0167] As an example, the composition of the CEI film may include one or more of LiF, Li3PO4, and Li2SO4.
[0168] In some embodiments, based on the total mass of the electrolyte, the mass content of the first additive is less than or equal to 7 wt %.
[0169] The mass content of the first additive is the ratio of the mass of the first additive to the mass of the electrolyte.
[0170] After formation, the mass of the first additive is consumed by about 5% to 90%. It should be noted that this refers to the consumption of the first additive of fresh lithium-ion battery cells compared to unformed lithium-ion battery cells. Fresh lithium-ion battery cells may refer to lithium-ion battery cells that have just been assembled on a vehicle, at which point the vehicle has not yet been driven or has a low mileage. The less mileage the vehicle has, the fresher the lithium-ion battery cells are.
[0171] Formation refers to the process of charging the assembled and injected lithium-ion battery cells for the first time. It should be understood that formation is a step in the preparation of lithium-ion battery cells. During the formation process, a CEI film and / or SEI film will be formed at the positive electrode and / or the negative electrode.
[0172] As an example, the mass content of the first additive is 0.5 wt % to 7 wt %.
[0173] Based on the total mass of the electrolyte, the mass content of the first additive can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt% or any value within the above range.
[0174] The setting of the first additive is conducive to forming a denser and more stable CEI and SEI film at the positive and negative electrodes, reducing the contact between carboxylic acid ester solvents and electrolytes, reducing the side reactions of carboxylic acid ester solvents, reducing the consumption of lithium ions, and improving the cycle life of lithium-ion battery cells; when the mass content of the first additive is less than or equal to 7wt%, it is conducive to reducing the increase in interface impedance caused by excessive mass content of the first additive, and the battery cell has a faster charging speed and a shorter charging time. In addition, it is also conducive to reducing the remaining amount of the first additive after formation. Therefore, when the mass content of the first additive is within the range of 0.5wt% to 7wt%, the battery cell can take into account both cycle life and fast charging performance.
[0175] In some embodiments, based on the total mass of the electrolyte, the mass content of the first additive is 1 wt % to 5 wt %. In this way, the lithium-ion battery cell can have both better fast charging performance and longer cycle life.
[0176] In some embodiments, based on the total mass of the electrolyte, the mass content of the first additive is 0 wt % to 4 wt %.
[0177] Based on the total mass of the electrolyte, the mass content of the first additive can be 0wt%, 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt% or any value within the above range.
[0178] Based on the total mass of the electrolyte, the mass content of the first additive is in the range of 0wt% to 4wt%, which is beneficial to reduce the risk of more side reactions due to the poor thermal stability and chemical stability of the first additive itself, thereby reducing the adverse effects on the cycle life of the lithium-ion battery cell.
[0179] In some embodiments, based on the total mass of the electrolyte, the mass content of the first additive is 0.01 wt % to 2.5 wt %. In this way, the lithium-ion battery cell can have a higher cycle life.
[0180] In some embodiments, the electrolyte further includes a second additive, and a reduction decomposition potential V2 of the second additive satisfies: 1.0V≤V1≤1.45V.
[0181] The reduction decomposition potential of the first additive and the reduction decomposition potential of the second additive are both electrode potentials relative to the same standard electrode. For example, in the embodiment of the present application, the reduction decomposition potential of the first additive and the reduction decomposition potential of the second additive are both electrode potentials relative to the lithium electrode.
[0182] The reductive decomposition potential of the second additive may be 1.0 V, 1.1 V, 1.2 V, 1.3 V, 1.4 V, 1.45 V, or any value within the above range.
[0183] The combination of the first additive and the second additive is conducive to further improving the cycle life of lithium-ion battery cells. The specific principle is speculated to be: the first additive and the second additive have different reduction decomposition potentials, which is conducive to the gradient formation of the SEI film, that is, at different stages of the charge and discharge cycle of the lithium-ion battery cell, the first additive and the second additive react at different potentials, so that the SEI film can be formed at different stages of the charge and discharge cycle of lithium ions, and the SEI film is denser and more stable. In addition, the first additive and the second additive can also form SEI films of different components. The second additive helps to form an SEI film rich in organic components. The SEI film rich in organic components has higher toughness, which can reduce the risk of the SEI film rich in inorganic components formed by the first additive being more brittle and ruptured in the later charge and discharge process, resulting in the continued side reaction of the carboxylic acid ester solvent at the negative electrode, thereby helping to further reduce the consumption of lithium ions.
[0184] In some embodiments, the second additive includes one or more of a carbonate compound, a sulfonate compound, a vinyl sulfate compound, or a sultone compound.
[0185] When the second additive meets the above-mentioned category and the reduction decomposition potential of the second additive is in the range of 1.0V to 1.45V, it helps to form a denser and more stable SEI film, and reduce the continued side reaction of the carboxylic acid ester solvent at the negative electrode caused by the rupture of the SEI film, thereby helping to reduce the consumption of lithium ions and improve the cycle life of the battery cell.
[0186] In some embodiments, the second additive includes one or more of methylene methanedisulfonate (MMDS), fluoroethylene carbonate (FEC), vinylene carbonate (VC), DTD, 2DTD, or propane sultone (PS, also referred to as 1,3-PS).
[0187] The structure of 2DTD is The structure of DTD is
[0188] The additives mentioned above help to form a CEI film at the positive electrode, inhibit the side reaction of the carboxylic acid ester solvent at the positive electrode, and thus help to reduce the consumption of lithium ions.
[0189] In some embodiments, the second additive includes at least one of MMDS, FEC, or PS.
[0190] The second additive is helpful to reduce the side reaction of the carboxylic acid ester solvent at the positive electrode and the negative electrode, and is also helpful to reduce the gas production and lithium ion consumption associated with the side reaction. Therefore, the second additive is not only helpful to improve the cycle life of the battery cell, but also helpful to reduce the gas production in the battery cell, thereby helping to reduce the pressure in the battery cell and improve the storage life of the battery cell.
[0191] In some embodiments, the second additive includes MMDS, FEC, and PS.
[0192] The addition of FEC results in a smaller increase in the impedance of the battery cell, which is beneficial to improving the cycle life of the battery cell while maintaining better fast charging performance. In addition, compared with VC, FEC is more resistant to oxidation, more conducive to reducing gas production and side reactions in the battery cell, and is better compatible with lithium transition metal oxides.
[0193] Furthermore, since FEC is conducive to the formation of a LiF-containing SEI film, through cooperation with MMDS and PS, it can not only achieve lower impedance and inhibit side reactions on the negative electrode side, but also help reduce problems such as the expansion of the battery cell caused by the continuous generation of the SEI film on the negative electrode side. Especially when matched with a silicon-containing negative electrode material, it can improve the energy density of the battery cell while taking into account smaller expansion.
[0194] In the above embodiment, it is conducive to forming a more stable SEI film, further reducing the side reactions of carboxylic acid ester solvents in the battery monomers, the consumption of lithium ions caused by the side reactions, and the gas production associated with the side reactions, and the battery monomers have longer cycle life and storage life.
[0195] In some embodiments, based on the total mass of the electrolyte, the mass content of the second additive is less than or equal to 12 wt %.
[0196] The mass content of the second additive is the ratio of the mass of the second additive to the mass of the electrolyte.
[0197] After formation, the mass of the second additive is consumed by about 5% to 90%. It should be noted that this refers to the consumption of the second additive of fresh lithium-ion battery cells compared to unformed lithium-ion battery cells. Fresh lithium-ion battery cells can refer to lithium-ion battery cells that have just been assembled on a vehicle, at which point the vehicle has not yet been driven. The less mileage the vehicle has, the fresher the lithium-ion battery cells are.
[0198] As an example, based on the total mass of the electrolyte, the mass content of the second additive is 0.5 wt % to 12 wt %.
[0199] Based on the total mass of the electrolyte, the mass content of the second additive can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt% or any value within the above range.
[0200] By setting the second additive, it is beneficial to form a more compact and stable CEI and SEI film at the positive and negative electrodes, reduce the contact between carboxylic acid ester solvents and electrolytes, reduce the side reactions of carboxylic acid ester solvents, reduce the consumption of lithium ions, and improve the cycle life of lithium-ion battery cells; when the mass content of the second additive is less than or equal to 12wt%, it is beneficial to reduce the increase in interface impedance caused by excessive mass content of the second additive, and the battery cell has a faster charging speed and a shorter charging time. In addition, it is also beneficial to reduce the remaining amount of the second additive after formation. Therefore, within the range of the mass content of the second additive being less than or equal to 12wt%, the battery cell can take into account both cycle life and fast charging performance.
[0201] In some embodiments, 2wt%≤W2≤9wt%. In this way, the lithium-ion battery cell can have both better fast charging performance and longer cycle life.
[0202] In some embodiments, the mass content of the second additive is 0 wt % to 10 wt % based on the total mass of the electrolyte.
[0203] Based on the total mass of the electrolyte, the mass content of the second additive can be 0wt%, 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or any value within the above range.
[0204] When the mass content of the second additive is within the range of 0wt% to 10wt% based on the total mass of the electrolyte, it is beneficial to reduce the risk of more side reactions due to the poor thermal and chemical stability of the second additive itself, thereby reducing the adverse effects on the cycle life of the lithium-ion battery cell.
[0205] In some embodiments, based on the total mass of the electrolyte, the mass content of the second additive is 0.01 wt % to 7 wt %. In this way, the lithium-ion battery cell can have a higher cycle life.
[0206] In some embodiments, based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is less than or equal to 16 wt %.
[0207] After the battery cell undergoes formation and charge-discharge cycles after formation, the first additive and the second additive will be consumed. After formation and charge-discharge cycles after formation, the sum of the mass contents of the first additive and the second additive may be 0 or a value greater than 0. For example, in the preparation process of a lithium-ion battery cell, when the sum of the mass contents of the first additive and the second additive is less than or equal to 0.5wt%, after formation, the sum of the mass contents of the first additive and the second additive is 0 or a value greater than 0 and close to 0. For another example, in the preparation process of a lithium-ion battery cell, when the mass content of the first additive exceeds 0.5wt%, there is a high probability that there will be a certain amount of residue of the first additive after formation; when the mass content of the second additive exceeds 0.5wt%, there is a high probability that there will be a certain amount of residue of the second additive after formation.
[0208] As an example, based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 16wt%. For example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.8wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt% or any value within the above range.
[0209] In the battery cell, when the sum of the mass content of the first additive and the second additive is less than or equal to 16wt%, it is conducive to forming a denser and more stable SEI film and CEI film at the negative electrode and the positive electrode, reducing the side reaction of the carboxylic acid ester solvent, reducing the consumption of lithium ions, and improving the cycle life of the lithium-ion battery cell. It can also reduce the increase in interface impedance caused by excessive mass content of the first additive and the second additive, and the battery cell has a faster charging speed and a shorter charging time. In this way, the battery cell can take into account both cycle life and fast charging performance.
[0210] In some embodiments, based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 3 wt % to 12 wt %. In this way, the lithium-ion battery cell can have both better fast charging performance and longer cycle life.
[0211] In some embodiments, based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 0 wt % to 14 wt %.
[0212] Based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive can be 0wt%, 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.8wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or any value within the above range.
[0213] Based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is in the range of 0wt% to 14wt%, and the residual amount of the first additive and the second additive is small, which is beneficial to reduce the risk of more side reactions due to the poor thermal stability and chemical stability of the first additive and / or the second additive itself, thereby reducing the adverse effects on the cycle life of the lithium-ion battery cell.
[0214] In some embodiments, based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 0.02 wt % to 10 wt %, which is beneficial to improving the cycle life of the lithium-ion battery cell.
[0215] In some embodiments, the first additive includes 3DTD and the second additive includes FEC. In this way, the battery cell has a longer cycle life.
[0216] In some embodiments, based on the total mass of the electrolyte, the mass content of the first additive is 1 wt % to 2 wt %, and the mass content of the second additive is 1 wt % to 2 wt %.
[0217] Based on the total mass of the electrolyte, the mass content of 3DTD in the first additive can be 1wt%, 1.5wt%, 2wt% or any value within the above range, and the mass content of FEC in the second additive can be 1wt%, 1.5wt%, 2wt% or any value within the above range.
[0218] In the above embodiment, the first additive and the second additive have relatively suitable mass contents, and the battery cell has a longer cycle life and a shorter fast charging time.
[0219] In some embodiments, the first additive includes 3DTD, LiDFOP, and LiDFOB, and the second additive includes MMDS, FEC, and PS.
[0220] In the first additive, the combination of 3DTD, LiDFOP and LiDFOB is beneficial to further improve the cycle life of the battery cell; in the second additive, MMDS, FEC and PS are beneficial to further improve the cycle life of the battery cell.
[0221] In some embodiments, based on the total mass of the electrolyte, the mass content of the first additive is 2 wt % to 4 wt %, and the mass content of the second additive is 5 wt % to 7 wt %.
[0222] Based on the total mass of the electrolyte, the sum of the mass contents of 3DTD, LiDFOP and LiDFOB in the first additive can be 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt% or any value within the above range, and the sum of the mass contents of MMDS, FEC and PS in the second additive can be 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt% or any value within the above range.
[0223] In the above embodiments, the battery cells have a longer cycle life and a shorter fast charging time.
[0224] In some embodiments, the positive electrode film layer further includes a conductive agent, and the conductive agent includes carbon nanotubes. In this way, the positive electrode plate has a smaller resistance, the temperature of the lithium-ion battery cell increases less when charging at a high current rate, and fewer side reactions occur in the lithium-ion battery cell, which helps to improve the cycle life of the lithium-ion battery cell. In addition, the conductive network formed by the carbon nanotubes is conducive to the transmission of electrons, which in turn helps the transmission of lithium ions, facilitates the use of the capacity of the lithium-ion battery cell, and helps to improve the cycle life of the lithium-ion battery cell.
[0225] In some embodiments, based on the total mass of the positive electrode film layer, the mass content A of the carbon nanotubes satisfies: 0.05 wt %≤A≤1 wt %.
[0226] A may be 0.05 wt%, 0.1 wt%, 0.15 wt%, 0.2 wt%, 0.5 wt%, 1 wt% or any value within the above range.
[0227] When A is greater than or equal to 0.05wt%, it helps to reduce the resistance of the positive electrode plate, thereby reducing the temperature rise of the lithium-ion battery cell, reducing the side reactions of the lithium-ion battery cell, and improving the cycle life of the lithium-ion battery cell; at the same time, it is also conducive to forming a better conductive network, facilitating the transmission of electrons and lithium ions, helping to exert the capacity, and further improving the cycle life of the lithium-ion battery cell. When A is less than or equal to 1wt%, it can reduce the risk of agglomeration of carbon nanotubes inside the positive electrode plate, improve the uniformity of electron and ion transmission inside the positive electrode plate, facilitate the capacity of the battery cell, and thus help improve the cycle life of the battery cell.
[0228] In the above embodiment, by setting 0.05wt%≤A≤1wt%, the carbon nanotubes have a suitable mass content, and the lithium-ion battery cell has a longer cycle life.
[0229] In some embodiments, 0.05 wt % ≤ A ≤ 0.5 wt %. In this way, the lithium-ion battery cell has a more suitable cycle life.
[0230] In some embodiments, the conductive agent further comprises carbon black, and based on the total mass of the positive electrode film layer, the mass content B of the carbon black satisfies: 0.1 wt % ≤ B ≤ 1 wt %.
[0231] B can be 0.1wt%, 0.15wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or any value within the above range.
[0232] When B is greater than or equal to 0.1wt%, it helps to reduce the resistance of the positive electrode plate; when B is less than or equal to 1wt%, the mass content of carbon black will not be too high, so that more positive electrode active materials can be added to the positive electrode film layer, which is beneficial to increase the capacity of the lithium-ion battery cell.
[0233] As an example, the carbon black is super conductive carbon black Super-p.
[0234] In some embodiments, based on the total mass of the positive electrode film layer, the sum of the mass contents of carbon black and carbon nanotubes is 0.05wt% to 2wt%. In this way, the conductive agent includes carbon black and carbon nanotubes, and the sum of the mass contents of carbon black and carbon nanotubes has a suitable range, and the lithium-ion battery cell can have a longer cycle life and a higher capacity.
[0235] In some embodiments, the carboxylate solvent includes: one or more of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl acrylate or ethyl acrylate. By selecting the above carboxylate solvent, the electrolyte has a lower viscosity and a higher ionic conductivity, which is beneficial to improving the fast charging performance of the lithium-ion battery monomer.
[0236] In some embodiments, the carboxylate solvent includes one or more of methyl acetate or ethyl acetate.
[0237] The viscosity and gas generation degree of carboxylic acid ester solvents are related to the chain length of the carboxylic acid ester solvents. Generally speaking, the more carbon atoms in the carboxylic acid ester solvents, the longer the chain length of the carboxylic acid ester solvents, the greater the viscosity of the carboxylic acid ester solvents, and the lower the gas generation degree.
[0238] The molecules of ethyl acetate and methyl acetate have suitable chain lengths. Ethyl acetate and methyl acetate have both low viscosity, which is beneficial to the diffusion and transmission of lithium ions, and a relatively suitable gas production level. By combining with the actuating pressure of the pressure relief mechanism in the embodiment of the present application, the lithium-ion battery cell can have better fast charging performance and better storage performance.
[0239] In some embodiments, the ionic conductivity of the electrolyte is 9 mS / cm to 23 mS / cm.
[0240] The ionic conductivity of the electrolyte may be 9 mS / cm, 11 mS / cm, 15 mS / cm, 16 mS / cm, 18 mS / cm, 20 mS / cm, 22 mS / cm, 23 mS / cm, or any value within the above range.
[0241] The electrolyte has a high ionic conductivity, which is conducive to the diffusion and transmission of lithium ions, and the lithium-ion battery cells have excellent fast charging performance.
[0242] In some embodiments, the ion conductivity of the electrolyte is 9 mS / cm to 18 mS / cm. In this way, the electrolyte has a higher ion conductivity, and the lithium-ion battery cell has a better fast charging performance.
[0243] In some embodiments, the viscosity of the electrolyte is 1 mm 2 / s~3mm 2 / s.
[0244] The viscosity of the electrolyte can be 1mm 2 / s、1.5mm 2 / s, 2mm 2 / s, 2.5mm 2 / s、3mm 2 / s or any value within the above range.
[0245] The viscosity of the electrolyte is 1 mm 2 / s~3mm 2 / s, which is conducive to the diffusion and transmission of lithium ions, and the lithium-ion battery monomer has better fast charging performance.
[0246] In some embodiments, the ionic conductivity of the electrolyte is 9 mS / cm to 15 mS / cm, and the viscosity of the electrolyte is 1.5 mm 2 / s~3mm 2 / s. The electrolyte can be compatible with positive electrode active materials including lithium transition metal oxides, which is beneficial to improving the fast charging performance of lithium-ion battery cells.
[0247] In some embodiments, based on the total mass of the electrolyte, the mass content W3 of the carboxylate solvent satisfies: 5wt%≤W3≤80wt%.
[0248] The mass content of the carboxylate solvent is the ratio of the mass of the carboxylate to the mass of the electrolyte.
[0249] W3 can be 5wt%, 10wt%, 15wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 78wt%, 80wt% or any value within the above range.
[0250] After formation, the mass of carboxylic acid ester solvents is consumed by about 1% to 15%. It should be noted that this refers to the consumption of carboxylic acid ester solvents in fresh lithium-ion battery cells compared to unformed lithium-ion battery cells. Fresh lithium-ion battery cells can refer to lithium-ion battery cells that have just been installed on a vehicle. At this time, the vehicle has not yet been driven or has a low mileage. The less mileage the vehicle has, the fresher the lithium-ion battery cells are.
[0251] For example, the mass content of the carboxylic acid ester solvent after formation is approximately in the range of 1 wt % to 78 wt %.
[0252] In addition, it should be noted that in the process of disassembling the lithium-ion battery monomer to obtain the electrolyte, the solvent in the electrolyte may volatilize. For example, based on the total mass of the electrolyte, the volatilized mass of the carboxylic acid ester solvent is about 1% to 10%.
[0253] When W3 is greater than or equal to 5wt%, the electrolyte has a lower viscosity, higher ionic conductivity, and the lithium-ion battery cell has a better fast-charging performance; when W3 is less than or equal to 80wt%, the risk of excessive consumption of active lithium ions due to excessive carboxylate solvents can be reduced, which is beneficial to improving the cycle life of lithium-ion battery cells. In this way, the battery cell can take into account both fast-charging performance and cycle life. In addition, when W3 is less than or equal to 80wt%, the gas production in the battery cell can also be reduced, and the gas production in the battery cell can be reduced.
[0254] In some embodiments, the carboxylate solvent includes methyl acetate, and based on the total mass of the electrolyte, the mass content W4 of methyl acetate satisfies: 5wt%≤W4≤80wt%.
[0255] W4 can be 5wt%, 7wt%, 10wt%, 15wt%, 20wt%, 30wt%, 35wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or any value within the above range.
[0256] Methyl acetate has high ion conductivity and low viscosity. When the mass content of methyl acetate is in the range of 5wt% to 80wt%, the lithium-ion battery monomer can have good fast charging performance.
[0257] In some embodiments, 15wt%≤W4≤30wt%.Methyl acetate has a suitable mass content, and the gas generation in the battery monomer is less, and the battery monomer has better comprehensive performance.
[0258] In some embodiments, the carboxylate solvent includes ethyl acetate, and based on the total mass of the electrolyte, the mass content W5 of ethyl acetate satisfies: 5wt%≤W5≤80wt%.
[0259] W5 can be 5wt%, 7wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 48wt%, 50wt% 60wt%, 70wt%, 80wt% or any value within the above range.
[0260] Ethyl acetate has a more suitable ionic conductivity and a lower viscosity, and the side reactions of ethyl acetate produce less gas. By setting the mass content of ethyl acetate to 5wt% to 80wt%, the lithium-ion battery cell can have better fast charging performance and cycle performance, as well as less gas production.
[0261] In some embodiments, 15wt%≤W5≤50wt%. In this way, the electrolyte can have a higher ion conductivity, and the battery cell can have a better fast charging performance.
[0262] In some embodiments, the carboxylate solvent includes ethyl acetate and methyl acetate, and based on the total mass of the electrolyte, the mass content of ethyl acetate is 5wt% to 80wt%, and the mass content of methyl acetate is 5wt% to 80wt%.
[0263] Ethyl acetate has more suitable ionic conductivity and viscosity and less gas production, while methyl acetate has higher ionic conductivity, lower viscosity and more suitable gas production. The combination of ethyl acetate and methyl acetate can balance the fast charging performance and gas production of lithium-ion battery cells, thereby taking into account the fast charging performance and storage life of lithium-ion battery cells.
[0264] In some embodiments, based on the total mass of the electrolyte, the mass content of ethyl acetate is 25 wt % to 50 wt %, and the mass content of methyl acetate is 15 wt % to 30 wt %.
[0265] The mass content of ethyl acetate can be 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 48wt%, 50wt%, or any value within the above range, and the mass content of methyl acetate can be 15wt%, 18wt%, 20wt%, 25wt%, 30wt% or any value within the above range.
[0266] In the above embodiment, ethyl acetate and methyl acetate have appropriate mass contents, and the lithium-ion battery cell has good fast charging performance and less gas production, thereby reducing the adverse effects of excessive gas production on the interface of the battery cell (such as lithium deposition at the negative electrode) and reliability.
[0267] In some embodiments, the electrolyte further includes a cyclic carbonate solvent and a linear carbonate solvent, the linear carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate, and the cyclic carbonate solvent includes one or more of ethylene carbonate or propylene carbonate.
[0268] As an example, carbonate solvents include ethylene carbonate and dimethyl carbonate. Dimethyl carbonate can improve the conductivity of the electrolyte, thereby improving the fast charging performance of lithium-ion battery cells. Ethylene carbonate can form a film on the surface of the negative electrode, reducing the side reaction between the carboxylate solvent and the negative electrode, which is beneficial to improving the cycle life of the lithium-ion battery cells.
[0269] Cyclic carbonates have a higher dielectric constant, which helps to increase the solubility of lithium salts in the electrolyte and thus help to increase the concentration of lithium salts in the electrolyte. Linear carbonate solvents have lower viscosity and electrochemical stability. Lower viscosity is conducive to the rapid migration of lithium ions in the electrolyte, improving the fast charging performance of lithium-ion battery cells; higher dielectric constants are conducive to increasing the solubility of lithium salts in the electrolyte and thus help to increase the concentration of lithium salts in the electrolyte; good electrochemical stability helps to increase the operating voltage range of lithium-ion battery cells, thereby increasing the capacity of lithium-ion battery cells. The combination of carbonate solvents and carboxylate solvents helps to improve the fast charging performance and cycle performance of lithium-ion battery cells.
[0270] In some embodiments, the solvent in the electrolyte includes methyl acetate, ethylene carbonate and dimethyl carbonate, and the electrolyte salt includes LiPF6. The above combination is conducive to improving the fast charging performance and cycle performance of the battery cell.
[0271] In some embodiments, the electrolyte further includes an electrolyte salt, and the electrolyte salt includes one or more of LiPF6 or LiFSI.
[0272] As an example, the electrolyte salt includes only LiPF6.
[0273] As another example, the electrolyte salt includes only LiFSI. LiFSI has high thermal stability, while the lithium-ion battery cell including lithium transition metal oxide generates high heat. By combining lithium transition metal oxide and LiFSI, the lithium-ion battery cell has high stability and reliability.
[0274] As another example, the electrolyte salt includes LiPF6 and LiFSI. LiFSI helps to form a LiF-rich SEI film, which can reduce the side reaction of carboxylic acid ester solvents at the negative electrode and improve the cycle life of lithium-ion battery cells.
[0275] For example, based on the total mass of the electrolyte salt, the mass content of LiFSI can be 2 wt% to 30 wt%. The mass content of LIFSI can be 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.2 wt%, 9 wt%, 10 wt%, 10.5 wt%, 11 wt%, 11.5 wt%, 12 wt%, 12.5 wt%, 13 wt%, 13.5 wt%, 14 wt%, 14.5 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 20 wt%, 22 wt%, 25 wt%, 28 wt%, 30 wt% or a numerical range between any two of the above.
[0276] In some embodiments, a lithium-ion battery cell includes: a negative electrode plate, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based material or a silicon-based material.
[0277] As an example, the negative electrode active material includes a carbon-based material or a silicon-based material.
[0278] As an example, the negative electrode active material includes silicon-based materials and carbon-based materials.
[0279] In some embodiments, the negative electrode active material includes a carbon-based material and a silicon-based material, and the mass content of silicon in the silicon-based material is 0.5 wt % to 50 wt % based on the total mass of the negative electrode active material.
[0280] Based on the total mass of the negative electrode active material, the mass content of silicon element in the silicon-based material can be 0.5wt%, 1wt%, 1.5wt%, 5wt%, 8wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt% or any value within the above range.
[0281] The negative electrode active material includes silicon-based materials, and the lithium-ion battery cell has a higher energy density; the mass content of silicon element meets the above range, and the lithium-ion battery cell has a more appropriate expansion rate, which can take into account both high energy density and high reliability. In addition, through the combination of silicon-based materials and the first additive and the second additive, the first additive and the second additive can form a film on the surface of the negative electrode and / or the positive electrode, reduce the subsequent side reactions on the negative electrode and / or the positive electrode side, reduce the thickness of the SEI film and CEI film of the battery cell throughout its life cycle, and reduce the expansion of the battery cell, thereby compensating to a certain extent for the large expansion of the lithium-ion battery cell caused by silicon-based materials, and the lithium-ion battery cell can take into account both high energy density and less expansion.
[0282] In some embodiments, based on the total mass of the negative electrode active material, the mass content of silicon in the silicon-based material is 0.5 wt % to 10 wt %. In this way, the lithium-ion battery cell can have both high energy density and high reliability.
[0283] In some embodiments, the carbon-based material includes a core portion and a second coating layer at least coated on the surface of the core portion, the core portion includes graphite, and the carbon-based material satisfies at least one of the following conditions: in the cumulative distribution curve of R values obtained by the carbon-based material in the surface scanning mode of a laser microscopy confocal Raman spectrometer, the R value R50 with a cumulative distribution of 50% is 0.15-0.50; in the R values of the obtained carbon-based materials, the number of R values less than or equal to 0.11 accounts for less than or equal to 15%; in the cumulative distribution curve of R values obtained by the carbon-based material in the surface scanning mode of a laser microscopy confocal Raman spectrometer, the concentration of R values (R90-R10) / R50 is less than or equal to 2.3; in all the R values obtained by the carbon-based material, the number of R values R50 with a cumulative distribution less than 50% of the core portion accounts for less than or equal to 10%.
[0284] The provision of the second coating layer is helpful to reduce the side reaction between graphite and carboxylic acid ester solvents, thereby helping to reduce the consumption of lithium ions and improve the cycle life of lithium ion battery cells.
[0285] The R value of carbon-based materials and the R value of the core refer to the ratio of the peak heights of the D-band and G-band of their Raman spectra. The D-band position is 1350±50cm -1 , G peak position is 1585±50cm -1 The R value can characterize the degree of defects and disorder of carbon-based materials. The larger the value, the greater the surface defects and the higher the surface disorder of the carbon-based material.
[0286] The R value cumulative distribution curve refers to arranging the 2500 R values obtained in order from small to large, and R50 is the R value corresponding to the 50% number arranged in order.
[0287] R50 can be 0.15, 0.18, 0.20, 0.22, 0.24, 0.26, 0.28, 0.30, 0.32, 0.34, 0.36, 0.38, 0.40, 0.42, 0.44, 0.46, 0.48, 0.50 or any range therebetween.
[0288] The R value R50 of the cumulative distribution of the carbon-based material at 50% is related to the R value of the cumulative distribution of the core at 50%, the R value of the cumulative distribution of the coating at 50%, the thickness of the coating, the uniformity of the coating, etc. For example, when other conditions are the same, the larger the R value of the cumulative distribution of the core at 50%, the larger the R value R50 of the cumulative distribution of the carbon-based material; the larger the thickness of the coating, the larger the R value R50 of the cumulative distribution of the carbon-based material.
[0289] R50 is 0.15 to 0.50, which is beneficial to reduce the degree of side reactions on the surface of carbon-based materials, reduce the consumption of lithium ions, and improve the cycle life of lithium-ion battery cells. It is also beneficial to improve the charge exchange capacity of lithium ions in the electrolyte on the surface of carbon-based materials, so that the liquid phase transmission rate of lithium ions matches the solid phase transmission rate, and improves the fast charging capacity of lithium-ion battery cells. In addition, it is also beneficial to use a lower content of the first additive and / or the second additive, so that the battery cell can have a higher fast charging capacity and a longer cycle life.
[0290] The cumulative distribution of the core graphite is 50% of the R value R50 generally does not exceed 0.11. Therefore, among all the R values of the obtained carbon-based materials, the proportion of the number of R values less than or equal to 0.11 can be used to indicate the degree of uncoating of the carbon-based material. The smaller the value, the smaller the degree of uncoating of the carbon-based material, the higher the surface coating of the carbon-based material, which is conducive to reducing the side reactions of graphite and carboxylic acid ester solvents and the co-embedding phenomenon of electrolyte solvents during the cycle, and the lithium-ion battery monomer has good cycle performance; in addition, the smaller the degree of uncoating of the carbon-based material, the higher the surface coating of the carbon-based material, the higher the isotropy of ion embedding, the charge exchange capacity of ions on the surface of the carbon-based material is improved, and then the solid-liquid transmission rate of lithium ions is increased, which can match with the electrolyte and improve the fast charging capacity of the lithium-ion battery monomer. In addition, the smaller the degree of uncoating of the carbon-based material, the more uniform the SEI film is formed on the surface of the carbon-based material, which is conducive to reducing the adverse effects of the uneven SEI film on the cycle life.
[0291] The concentration of R values is expressed as (R90-R10) / R50, where R90 is the R value with a cumulative distribution of 90% from the lower limit, R10 is the R value with a cumulative distribution of 10% from the lower limit, and R50 is the R value with a cumulative distribution of 50% from the lower limit. That is, the 2500 R values obtained are arranged in order from small to large, R10 is the R value corresponding to the 10% number in the order, R50 is the R value corresponding to the 50% number in the order, and R90 is the R value corresponding to the 90% number in the order.
[0292] The concentration of R value is small, the distribution width of R value is narrow, the concentration is good, and the coating layer has good consistency.
[0293] The concentration of R value can be 1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3 or any value within the above range. By setting the concentration of R value (R90-R10) / R50 to be less than or equal to 2.3, the second coating layer has better consistency, which is beneficial to reduce the side reaction between graphite and carboxylic acid ester solvents, and the lithium-ion battery monomer has a longer cycle life. In addition, the better the consistency of the second coating layer, the better the consistency of the SEI film formed on the surface of the carbon-based material, which is beneficial to improve the cycle life of the lithium-ion battery monomer.
[0294] Among all the R values obtained by the carbon-based material, the proportion of the number of R values R50 less than 50% of the cumulative distribution of the core can reflect the degree of non-coating of the carbon-based material. Among all the R values obtained by the carbon-based material, the proportion of the number of R values R50 less than 50% of the cumulative distribution of the core can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value within the above range. The smaller the value, the smaller the degree of non-coating of the carbon-based material, which is beneficial to improving the cycle performance of lithium-ion battery monomers.
[0295] Among all R values obtained by setting the carbon-based material, the number of R values R50 less than 50% of the cumulative distribution of the core portion accounts for less than or equal to 10%, and the lithium-ion battery cell has a higher cycle life.
[0296] In some embodiments, the carbon-based material satisfies at least one of the following conditions: in the cumulative distribution curve of R values obtained by the carbon-based material in the surface scanning mode of the laser micro-confocal Raman spectrometer, the R value R50 with a cumulative distribution of 50% is 0.15-0.30; in the R values of the obtained carbon-based materials, the number of R values less than or equal to 0.11 accounts for less than or equal to 10%; in the cumulative distribution curve of R values obtained by the carbon-based material in the surface scanning mode of the laser micro-confocal Raman spectrometer, the concentration of R values (R90-R10) / R50 is less than or equal to 1.7; among all the R values obtained by the carbon-based material, the number of R values R50 with a cumulative distribution of less than 50% in the core accounts for less than or equal to 6%.
[0297] When R50 is 0.15 to 0.30, it is beneficial to reduce the degree of side reactions on the surface of the carbon-based material.
[0298] Among the R values of the obtained carbon-based materials, the number of R values less than or equal to 0.11 accounts for less than or equal to 10%. The degree of coating of the carbon-based materials is high, which is beneficial to reducing the degree of side reactions on the surface of the carbon-based materials and the co-embedding phenomenon of the electrolyte solvent during the cycle process. The lithium-ion battery monomer has good cycle performance.
[0299] When R50 is 0.15-0.30 and the number of R values less than or equal to 0.11 accounts for less than or equal to 10%, the surface disorder of the carbon-based material is within the above range and the degree of coating is high, which is beneficial to reduce the degree of side reactions on the surface of the carbon-based material and the co-embedding phenomenon of the electrolyte solvent during the cycle, and the lithium-ion battery monomer has good cycle performance.
[0300] The concentration of R value (R90-R10) / R50 is less than or equal to 1.7, which is conducive to further improving the cycle performance of lithium-ion battery cells.
[0301] Among all the R values obtained by the carbon-based materials, the number of R values R50 less than 50% of the cumulative distribution of the core accounts for less than or equal to 6%, which is beneficial to further improve the cycle performance of lithium-ion battery cells.
[0302] In some embodiments, in the R value cumulative distribution curve obtained by the laser microscopic confocal Raman spectrometer surface scanning mode, the R value R50 with a cumulative distribution of 50% is 0.15 to 0.30. In this way, the surface disorder of the carbon-based material is within the above range, which is conducive to reducing the degree of side reactions on the surface of the carbon-based material, and the lithium-ion battery monomer has better cycle performance.
[0303] In some embodiments, among the R values of the obtained carbon-based materials, the number of R values less than or equal to 0.11 accounts for less than or equal to 6%. In this way, the carbon-based material has a high degree of coating, which is conducive to reducing the degree of side reactions on the surface of the carbon-based material and the co-embedding phenomenon of the electrolyte solvent during the cycle, and the lithium-ion battery monomer has good cycle performance.
[0304] In some embodiments, the air oxidation temperature T0 of the carbon-based material is 630°C to 730°C, wherein the air oxidation temperature T0 is the temperature corresponding to the intersection of two tangents at two points corresponding to 500°C and T1 temperatures on the thermogravimetric curve of the carbon-based material, respectively, and the T1 temperature is the peak temperature of the maximum area peak in the differential thermogravimetric curve of the carbon-based material. The thermogravimetric curve and the differential thermogravimetric curve can be obtained by thermogravimetric analysis under the following conditions: sample mass 10±0.05 mg, purge gas is air and the airflow rate is 60 mL / min, the heating rate is 5°C / min, and the test temperature range is 35°C to 950°C.
[0305] The oxidation of carbon-based materials in the air often starts from surface defects. Therefore, the temperature corresponding to the intersection of the two tangents at the two points corresponding to 500°C and the peak temperature T1 of the maximum area peak on the thermogravimetric curve, that is, the air oxidation temperature T0 of the carbon-based material, can accurately indicate the temperature when it starts to lose weight due to air oxidation, and can reflect the number of surface defects of the carbon-based material.
[0306] The air oxidation temperature T0 of the carbon-based material can be 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C or any range therebetween.
[0307] The negative electrode active material with an air oxidation temperature T0 of 630°C to 730°C has an appropriate number of surface defects, which makes the degree of side reactions of the battery cell within a controllable range. At the same time, it can also provide sufficient end surfaces for the embedding of active ions and match the lithium ion transfer rate of the electrolyte. Therefore, the battery cell can have improved fast charging performance while maintaining the cycle life.
[0308] In some embodiments, the carbon-based material includes secondary particles formed by agglomeration of primary particles, and the volume average particle size of the carbon-based material is 8 μm to 18 μm.
[0309] The volume average particle size of the carbon-based material may be 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm or any range therebetween.
[0310] Carbon-based materials include secondary particles formed by agglomeration of primary particles, which means that the negative electrode active material mainly includes secondary particles formed by agglomeration of primary particles. That is, more than 85% of the particles in the carbon-based material are secondary particles. This can be determined by observing the particle morphology of the cross section in the thickness direction of the negative electrode sheet.
[0311] On the one hand, the carbon-based materials with a volume average particle size within the above range can make use of a certain number of primary particles in the secondary particles to make the carbon-based materials have a suitable embedding surface, and the solid-phase transmission rate and solid-liquid transmission rate of active ions in the carbon-based materials can match the liquid-phase transmission rate of lithium ions in the electrolyte, thereby improving the fast charging performance of the battery; on the other hand, it can also have the advantages of high compaction density and large capacity of secondary particles, thereby improving the fast charging performance of the battery while taking into account the energy density of the battery cell.
[0312] In some embodiments, the carbon-based material includes unagglomerated primary particles, and the volume average particle size of the carbon-based material is 5 μm to 13 μm.
[0313] The volume average particle size of the carbon-based material may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm or any range therebetween.
[0314] The carbon-based material includes unagglomerated primary particles, which means that more than 85% of the particles in the carbon-based material are unagglomerated primary particles. This can be determined by observing the particle morphology of the cross section in the thickness direction of the negative electrode sheet.
[0315] Carbon-based materials with a volume average particle size within the above range have higher interface stability than particles with smaller particle sizes, which helps to reduce the extent of side reactions in battery cells and improve the cycle life of battery cells.
[0316] In some embodiments, the core of the carbon-based material includes artificial graphite, and the second coating layer includes amorphous carbon.
[0317] Amorphous carbon refers to a carbon material with a very low degree of graphitization and a nearly amorphous form (or no fixed shape and periodic structural regularity). There is no regular arrangement between the carbon atoms in the amorphous carbon structure. Therefore, amorphous carbon can be characterized by transmission electron microscopy (TEM) testing. By cutting a thin slice of about 100nm thickness from the middle of the negative electrode active material particles using a focused ion beam (FIB), and then performing a TEM test on the slice, it can be observed that the surface area includes the second coating layer. The lattice fringes in the second coating layer show long-range disorder and short-range order, and the electron diffraction pattern shows a halo shape, which indicates that the second coating layer includes amorphous carbon.
[0318] Artificial graphite has fewer defects and higher capacity, which can reduce the degree of side reactions with the electrolyte, give full play to the high capacity characteristics of graphite, reduce gas production, and enable the battery cells to have both high energy density and good cycle performance.
[0319] Amorphous carbon has a high hardness and therefore has good compressive resistance. It has a strong ability to maintain the pore structure of the negative electrode film during the cycle and has better electrolyte wettability of the negative electrode plate, so it is also beneficial to improve the cycle performance of the battery cell.
[0320] In some embodiments, the surface density of the negative electrode sheet is 0.05 mg / mm 2 ~0.11mg / mm 2 , and / or, the compaction density of the negative electrode sheet is 1.2g / cm 3~ 1.7g / cm 3 .
[0321] The surface density of the negative electrode sheet can be 0.05 mg / mm 2 , 0.06mg / mm 2 , 0.07mg / mm 2 , 0.08mg / mm 2 , 0.09mg / mm 2 , 0.10mg / mm 2 、0.11mg / mm 2 Or any value within the above range, the compaction density of the negative electrode sheet can be 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm3 , 1.6g / cm 3 , 1.7g / cm 3 Or any value within the above range.
[0322] After formation and a certain number of charge and discharge cycles, the surface density of the negative electrode sheet remains basically unchanged, but the thickness of the negative electrode sheet increases and the compaction density of the negative electrode sheet decreases. Compared with the compaction density after cold pressing, the compaction density of the lithium-ion battery cell in the entire life cycle is reduced by about 0 to 1 g / cm 3 Specifically, as an example, a lithium-ion battery cell after charge and discharge cycles is disassembled, and the compaction density of the negative electrode obtained from the disassembly is tested. The compaction density obtained by the test is added with 1g / cm 3 If the compaction density still falls within the range of the compaction density of the present application, it can be inferred that the compaction density of the embodiment in the present application is adopted.
[0323] By combining the carboxylic acid ester solvent of the present application with the surface density and the compaction density, the lithium-ion battery monomer can have a better fast charging performance while having a larger surface density and compaction density.
[0324] In some embodiments, the lithium transition metal oxide may include, but is not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds.
[0325] In some embodiments, the chemical formula of the lithium transition metal oxide satisfies: Li 1+a [Ni x Co y Mn z M b ]O 2-c A f, M includes one or more of Zr, Al, Ti, Sb, Nb, Te, Mg, B, Ca, V, Ta or Sr, 0.2≥a≥-0.2, 1>x>0, 1>y>0, 1>z>0, 1>b≥0, 0.5≥c≥0, 0≤f≤1. Wherein, x+y+z+b=1, a can be 0.2, 0.1, 0, -0.1, -0.2 or any value within the above range, x can be 0.7, 0.68, 0.65, 0.5, 0.4, 0.3 or any value within the above range, y can be 0.07, 0.08, 0.1, 0.12, 0.3, 0.5, 0.7, 0.8 or any value within the above range, z can be 0.05, 0.1, 0.2, 0. .25, 0.3, 0.5, 0.7, 0.8 or any value within the above range, b can be 0.05, 0.1, 0.2, 0.25, 0.3, 0.5, 0.7, 0.8 or any value within the above range, c can be 0, 0.1, 0.2, 0.3, 0.4, 0.5 or any value within the above range, and f can be 0, 0.1, 0.3, 0.5, 0.6, 0.8, 0.9 or any value within the above range.
[0326] Lithium transition metal oxides may include but are not limited to LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.80 Co 0.15 Al 0.05 O2、LiNi 0.9 Co 0.06 Mn 0.04 O2、LiNi 0.92 Co 0.06 Mn 0.02 O2、LiNi 0.96 Co 0.02 Mn 0.02 O2、LiNi 0.55 Co 0.07 Mn 0.38 O2、LiNi 0.55 Co 0.12 Mn 0.33 O2、LiNi 0.65 Co 0.1 Mn 0.25 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2、LiNi 0.6 Co 0.1 Mn 0.3 One or more of O2.
[0327] The battery is accompanied by Li deintercalation and consumption during the charge and discharge process. The molar content of Li in the positive electrode active material is different when the battery is discharged to different states.
[0328] In the enumeration of lithium transition metal oxides in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The lithium transition metal oxide is used in the battery system, and the molar content of Li will change after the charge and discharge cycle. In the enumeration of lithium transition metal oxides in this application, the molar content of O is only the ideal state value. The lattice oxygen release will cause the molar content of O to change, and the actual molar content of O will fluctuate.
[0329] In some embodiments, the lithium transition metal oxide includes lithium nickel cobalt manganese oxide.
[0330] In some embodiments, the lithium transition metal oxide includes unagglomerated primary particles.
[0331] In this application, a primary particle refers to the smallest unit of a particle within a certain observation range. A primary particle may contain any form of defects, but it is impossible to define a smaller particle in a primary particle. Primary particles may aggregate under physical effects such as van der Waals forces, but such aggregation is easily deaggregated under external forces such as ultrasound, stirring, and rolling, so that the main component form of the lithium transition metal oxide in the film layer is still primary particles.
[0332] In the present application, secondary particles are formed by the agglomeration of primary particles. The agglomeration here is a hard agglomeration caused by chemical bonding of primary particles, so that the secondary particles have a clear surface and boundary, and are not easily dispersed under external forces such as ultrasound; however, after cutting the cross section of the secondary particles, it can be seen that the secondary particles are formed by the agglomeration of many primary particles.
[0333] In this embodiment, the lithium transition metal oxide includes unagglomerated primary particles, that is, a powder mainly composed of unagglomerated primary particles. Compared with lithium transition metal oxides of secondary particles, the use of lithium transition metal oxides of unagglomerated primary particles is conducive to reducing the degree of side reactions between lithium transition metal oxides and carboxylic acid ester solvents, which is conducive to further improving the cycle life of lithium-ion battery monomers.
[0334] In some embodiments, the volume average particle size of the lithium transition metal oxide is 2 μm to 5 μm.
[0335] The volume average particle size of the material can be represented by Dv50, which represents the particle size corresponding to the cumulative volume distribution percentage of 50%, and can be measured by instruments and methods known in the art. For example, it can be conveniently measured by a laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method. The test instrument can be the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.
[0336] In the case where the lithium transition metal oxide includes unagglomerated primary particles, the volume average particle size of the lithium transition metal oxide may be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, or any range therebetween.
[0337] The degree of side reaction between the lithium transition metal oxide within the above particle size range and the carboxylic acid ester solvent is low, which is beneficial to further improve the cycle life of the lithium ion battery monomer.
[0338] In some embodiments, the lithium transition metal oxide satisfies at least one of the following conditions: based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of cobalt is less than or equal to 20%; based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of nickel is less than 80%.
[0339] Based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of cobalt can be 20%, 18%, 16%, 15%, 12%, 10%, 9%, 7%, 5%, 3%, 1%, 0.5% or any value within the above range. The molar content of cobalt less than or equal to 20% is conducive to reducing the cost of positive electrode active materials, and by matching with primary particles of unagglomerated lithium transition metal oxides with a volume average particle size of 2μm to 5μm, it is conducive to reducing the side reactions between lithium transition metal oxides and carboxylic acid ester solvents, and at the same time, it is conducive to improving the kinetic properties of lithium transition metal oxides.
[0340] Based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of nickel can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 79% or any range of values therebetween. Setting the molar content of nickel to meet the above range is beneficial to reducing the probability of nickel dissolution of the lithium transition metal oxide under high voltage, and the combination with unagglomerated primary particles is also beneficial to reducing the degree of side reactions between the lithium transition metal oxide and carboxylic acid ester solvents, thereby improving the cycle performance of lithium-ion battery monomers.
[0341] In some embodiments, the lithium transition metal oxide satisfies at least one of the following conditions: based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of cobalt accounts for 5% to 12%; based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of nickel accounts for 65% to 70%.
[0342] Setting the molar content of cobalt to 5% to 12% is beneficial to taking into account both the cycle performance and fast charging performance of the lithium-ion battery cell.
[0343] Setting the molar content of nickel to 65% to 70% is also beneficial to reducing the degree of side reactions between lithium transition metal oxides and carboxylic acid ester solvents and improving the cycle performance of lithium ion battery monomers.
[0344] In some embodiments, the lithium transition metal oxide includes secondary particles formed by agglomeration of primary particles, and the lithium transition metal oxide satisfies at least one of the following conditions: the volume average particle size of the lithium transition metal oxide is 6 μm to 15 μm; the average particle size of the primary particles in the secondary particles is 0.1 μm to 1.5 μm; based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of nickel is greater than or equal to 80%.
[0345] Based on the total moles of transition metals in the lithium transition metal oxide, the molar content of nickel can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or any range therebetween.
[0346] The volume average particle size of the lithium transition metal oxide can be 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or any range therebetween. Forming the high nickel material into large-sized secondary particles is beneficial to simultaneously increasing the specific capacity of the lithium transition metal oxide and improving the energy density of the lithium-ion battery monomer.
[0347] The average particle size of the primary particles in the secondary particles can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm or any range of values therebetween. The secondary particles are composed of primary particles of small particle size, which can shorten the transmission distance of lithium ions, increase the number of embedded end faces, reduce the DC impedance of the battery cell, and improve the fast charging performance of the battery cell.
[0348] In some embodiments, in the particles of lithium transition metal oxide, the mass proportion of cobalt elements near the surface of the particle is greater than the mass proportion of cobalt elements near the center of the particle, wherein the area near the surface of the particle is the area from the surface of the particle to a depth of 200 nm in the direction toward the geometric center of the particle, and the area near the center of the particle is a spherical area with a diameter of 200 nm and the geometric center of the particle cross section as the center of the circle.
[0349] The relatively high cobalt content on the surface of lithium transition metal oxides helps to improve the ionic conductivity of lithium transition metal oxides, improve the problem of lithium over-desorption on the surface of lithium transition metal oxides during charging and discharging, inhibit and reduce the cation mixing of the Li layer and the transition metal layer, stabilize the layered structure of lithium transition metal oxides, and reduce the risk of structural phase change on the surface of lithium transition metal oxides, thereby reducing the degree of side reactions of battery cells and improving the cycle life of battery cells. The relatively low cobalt content in the center of lithium transition metal oxides can simultaneously reduce the cost of lithium transition metal oxides.
[0350] In some embodiments, the ratio of the mass proportion of the cobalt element near the particle surface to the mass proportion of the cobalt element near the center of the particle is 1.01 to 5. This helps to stabilize the layered structure of the lithium transition metal oxide and reduce the risk of structural phase change on the surface of the lithium transition metal oxide, thereby reducing the degree of side reactions of the battery monomer and improving the cycle life of the battery monomer.
[0351] The ratio of the mass fraction of the cobalt element near the surface of the particle to the mass fraction of the cobalt element near the center of the particle can be 1.01, 1.05, 1.1, 1.15, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5 or any range of values therebetween.
[0352] In some embodiments, the ratio of the mass fraction of the cobalt element near the particle surface to the mass fraction of the cobalt element near the particle center is 1.4-2.
[0353] In some embodiments, the lithium transition metal oxide includes a substrate and a first coating layer covering at least a portion of a surface of the substrate, wherein the first coating layer includes at least one of V, Mo, Ti, Al, or O elements.
[0354] As an example, the coating layer on the surface of the substrate of the lithium transition metal oxide can be observed by a scanning electron microscope SEM, and further, the elements in the coating layer can be tested in combination with an energy dispersive spectrometer EDS.
[0355] As an example, the substance in the coating layer exists in the form of metal oxides. For example, the coating layer includes at least one of Li3V(MoO4)3, TiO2, and Al2O3.
[0356] In the above embodiment, the provision of the first coating layer is helpful to reduce the side reaction of the carboxylate solvent at the positive electrode, reduce the consumption of lithium ions, and improve the cycle life of the lithium-ion battery cell.
[0357] In some embodiments, part of the surface of the substrate of the lithium transition metal oxide is not covered with the first coating layer, that is, there is an uncoated area on the surface of the substrate of the lithium transition metal oxide.
[0358] In some embodiments, the positive electrode active material further includes a lithium-containing phosphate.
[0359] The lithium-containing phosphate refers to a phosphate having an olivine structure such as lithium iron phosphate.
[0360] As an example, the positive electrode active material includes a lithium-containing phosphate and a lithium transition metal oxide, wherein the lithium-containing phosphate is lithium iron phosphate and the lithium transition metal oxide is LiNi 0.65 Co 0.07 Mn 0.28 In the above case, the mass content of the lithium-containing phosphate can be determined by testing the mass ratio of the Fe element (or P element) and the Ni element in the positive electrode sheet.
[0361] Compared with lithium-ion battery cells that only include lithium transition metal oxides, lithium-ion battery cells that include lithium phosphate and lithium transition metal oxides have smaller impedance in a lower SOC range, which is beneficial to improving the power of lithium-ion battery cells. For example, when the battery cells are applied to electric vehicles, the electric vehicles have a faster starting speed.
[0362] In some embodiments, the mass content of the lithium-containing phosphate is 1 wt % to 50 wt % based on the total mass of the positive electrode active material.
[0363] Based on the total mass of the positive electrode active material, the mass content of the lithium phosphate can be 1wt%, 1.5wt%, 2wt%, 3wt%, 5wt%, 8wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt% or any value within the above range.
[0364] When the mass content of the lithium-containing phosphate is 1wt% to 50wt% based on the total mass of the positive electrode active material, the lithium-containing phosphate and the lithium transition metal oxide both have relatively suitable mass contents, which can take into account the energy density, cycle performance and power of the lithium-ion battery monomer, and the lithium-ion battery monomer has good comprehensive performance.
[0365] In some embodiments, the mass content of the lithium-containing phosphate is 1 wt% to 5 wt% based on the total mass of the positive electrode active material. In this way, the energy density, cycle performance and power of the lithium-ion battery cell can be well balanced, and the lithium-ion battery cell has good comprehensive performance.
[0366] In some embodiments, the lithium-containing phosphate has an olivine structure, including but not limited to one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, and their respective doped modified materials, coated modified materials, and composite modified materials.
[0367] In some embodiments, the lithium-containing phosphate includes at least one of lithium iron phosphate, lithium manganese phosphate, or lithium manganese iron phosphate.
[0368] In some embodiments, the single-side density of the positive electrode sheet is 0.09 mg / mm 2 ~0.15mg / mm 2 , and / or, the compaction density of the positive electrode sheet is 2.0g / cm 3 ~3.8g / cm 3 .
[0369] The single-side density of the positive electrode sheet can be 0.09 mg / mm 2 , 0.1mg / mm 2 、0.11mg / mm 2 , 0.12mg / mm 2 , 0.13mg / mm 2 , 0.14mg / mm 2 , 0.15mg / mm 2 Or any value within the above range, the compaction density of the positive electrode sheet can be 2.0g / cm 3 , 2.2g / cm 3 , 2.5g / cm 3 , 2.8g / cm 3 、3.0g / cm 3 、3.2g / cm 3 、3.4g / cm 3 、3.5g / cm 3 、3.6g / cm 3 、3.8g / cm 3 Or any value within the above range.
[0370] After formation and a certain number of charge and discharge cycles, the surface density of the positive electrode sheet remains basically unchanged, but the thickness of the positive electrode sheet increases and the compaction density of the positive electrode sheet decreases. Compared with the compaction density after cold pressing, the compaction density of the lithium-ion battery cell in the entire life cycle is reduced by about 0 to 1 g / cm 3Specifically, as an example, a lithium-ion battery cell after charge and discharge cycle is disassembled, and the compaction density of the positive electrode sheet and the negative electrode sheet obtained by disassembly is tested. The compaction density obtained by the test is added with 1g / cm 3 If the compaction density still falls within the range of the compaction density of the present application, it can be inferred that the compaction density of the embodiment in the present application is adopted.
[0371] When the surface density and compaction density of the positive electrode sheet are large, the diffusion of lithium ions is affected to a certain extent, and the improvement of the fast charging performance of the lithium-ion battery monomer is small. By combining the carboxylic acid ester solvent of the present application with the surface density and compaction density, the lithium-ion battery monomer can have better fast charging performance when having a large surface density and compaction density.
[0372] In some embodiments, the material of the housing 30 includes steel, and the thickness of the housing 30 is 0.1 mm to 0.5 mm.
[0373] In the case where the material of the housing 30 includes steel, the thickness of the housing 30 may be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, or any value within the above range.
[0374] As an example, the housing 30 includes a shell 31 and an end cover 32 , and the thickness of the shell 31 and the end cover 32 both meet the above range.
[0375] In the case where the material of the outer case 30 includes steel, by setting the thickness of the outer case 30 to 0.1 mm to 0.5 mm, the outer case has higher strength, and the lithium ion battery including the plurality of lithium ion battery cells can have higher volume energy density.
[0376] In some embodiments, the thickness of the outer shell is 0.2 mm to 0.3 mm, which is conducive to further taking into account the strength of the outer shell and the volume energy density of the lithium-ion battery.
[0377] Steel has high strength, and by setting the material of the outer shell to include steel, the outer shell 30 can match the pressure inside the lithium-ion battery cell.
[0378] In some embodiments, the material of the outer shell includes aluminum, and the thickness of the outer shell 30 is 0.3 mm to 1.0 mm.
[0379] When the material of the housing 30 includes aluminum, the thickness of the housing 30 may be 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, or any value within the above range.
[0380] Aluminum has high strength and relatively suitable processing performance. By setting the material of the shell 30 to include aluminum, it is easy to prepare the shell 30, and the shell 30 also has relatively suitable strength. By setting the thickness of the shell 30 to 0.3mm-1.0mm, during the normal use of the lithium-ion battery cell, the shell 30 is not easy to break, the risk of the pressure relief mechanism 313 actuating the valve in advance is low, and the lithium-ion battery cell has high reliability and long storage time.
[0381] In some embodiments, the thickness of the outer shell is 0.5 mm to 0.6 mm, which is conducive to further taking into account the strength of the outer shell and the volume energy density of the lithium-ion battery.
[0382] The shell 31 and the end cover 32 may have the same thickness or different thicknesses.
[0383] As an example, the material of the housing 30 includes steel, and the shell 31 and the end cover 32 have the same thickness.
[0384] As another example, the material of the housing 30 includes aluminum, and the thickness of the end cap 32 is greater than the thickness of the shell 31 .
[0385] In some embodiments, the time t for charging a lithium-ion battery cell from 10% SOC to 80% SOC satisfies: t≤15 min. The lithium-ion battery cell including lithium transition metal oxide has a shorter charging time and better fast charging performance.
[0386] In some embodiments, the time t for charging the lithium-ion battery cell from 10% SOC to 80% SOC satisfies: t≤10 min. In this way, the lithium-ion battery cell has a shorter charging time and better fast charging performance.
[0387] The above charging time is the charging time of a lithium-ion battery cell at 25°C to 35°C, and the charging time reflects the fast charging capability of the lithium-ion battery cell. During the fast charging process of a lithium-ion battery cell, the current density (or rate) is usually not constant, but variable.
[0388] In some embodiments, when the charging rate of the lithium-ion battery is greater than or equal to 2.8C, the charging time from 10% SOC to 80% SOC is less than or equal to 15 minutes. This rate is the equivalent charging rate of the lithium-ion battery cell in the process of charging from 10% SOC to 80% SOC. In other words, in the process of charging from 10% SOC to 80% SOC, the charging rate may gradually decrease from greater than 2.8C to less than 2.8C. In this process, the lithium-ion battery cell may undergo a transition from constant current charging to constant voltage charging, so the current is not constant. For example: start charging the lithium-ion battery cell at a normal temperature of 25°C, charge from 10% SOC to 80% SOC, and the charging time is 10 minutes (equivalent charging rate ≥ 4C). The charging process is: initially at 5C from 10% SOC to 45% SOC, then at 4.6C from 45% SOC to 50% SOC, 4.3C from 50% SOC to 55% SOC, 3.9C from 55% SOC to 60% SOC, 3.6C from 60% SOC to 65% SOC, 3.3C from 65% SOC to 70% SOC, 3.1C from 70% SOC to 75% SOC, 2.9C from 75% SOC to 80% SOC, and the charging is completed. The charging time for a lithium-ion battery cell to charge from 0% SOC to 100% SOC at 1C is 60 minutes. Therefore, when it is measured that the charging time of the lithium-ion battery cell from 10% SOC to 80% SOC is 10 minutes, the equivalent charging rate of the process can be calculated as: [(80% SOC-10% SOC) / (100% SOC-0% SOC)]×[(1C×60min) / 10min]=4.2C.
[0389] If a lithium-ion battery cell is placed on a charging station for charging, the time it takes to charge from 10% SOC to 80% SOC can also be directly recorded.
[0390] When the vehicle is charging at a charging pile, the charging curve will be displayed on the charging pile system (the charging curve may be seen on the charging pile display screen, on the mobile phone charging control APP, in the battery monitoring background, etc.). For example, the horizontal axis is the charging time, and the vertical axis is the charging power and charging SOC. The charging power and SOC of the vehicle's battery at different times can be seen from the charging curve, and the charging time of 20% SOC-80% SOC or 10% SOC-80% SOC can also be read from the charging curve.
[0391] In this application, a charging time of less than 15 minutes from 10% SOC to 80% SOC is considered fast charging, and the battery used in the vehicle is a fast charging battery. In addition, if the vehicle or battery manual mentions that the charging time of 10% SOC to 80% SOC is less than 15 minutes, it also belongs to the fast charging battery mentioned in this application.
[0392] The present invention has no particular restrictions on the shape of the lithium-ion battery cell, which may be cylindrical, square, or any other shape. Figure 2 As shown, the lithium-ion battery cell 3 is a square lithium-ion battery cell. The lithium-ion battery cell 3 includes a housing 31 , an end cover 32 and an electrode assembly 33 disposed in the housing 31 .
[0393] The electrode assembly 33 may be made of a positive electrode sheet, a negative electrode sheet and a separator by a winding process or a lamination process. The electrode assembly 33 may include an electrode assembly body and a tab 331 extending from the electrode assembly body.
[0394] The end cap 32 includes an electrode terminal 322, such as Figure 2 As shown, the end cap 32 includes two electrode terminals 322, one of which is a positive electrode terminal and the other is a negative electrode terminal.
[0395] The lithium-ion battery cell 3 further includes a connecting member 34, which is used to connect the tab 331 of the electrode assembly 33 and the electrode terminal 322. For example, one connecting member 34 is used to connect the positive tab and the positive electrode terminal, and another connecting member 34 is used to connect the negative tab and the negative electrode terminal.
[0396] In some embodiments, lithium-ion battery cells can be assembled into a battery module. The number of lithium-ion battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0397] [Positive electrode]
[0398] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.
[0399] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0400] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0401] In some embodiments, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and its modified compounds, etc. One or more. The battery will be accompanied by the deintercalation and consumption of Li during the charging and discharging process, and the molar content of Li in the positive electrode active material is different when the battery is discharged to different states. In the enumeration of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after the charge and discharge cycle. In the enumeration of positive electrode active materials in this application, the molar content of O is only an ideal state value. Lattice oxygen release will cause the molar content of O to change, and the actual molar content of O will fluctuate.
[0402] In some embodiments, the positive electrode film layer further includes a binder. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0403] In some embodiments, the positive electrode film layer further includes a conductive agent. As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0404] In one embodiment, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet are formed into a positive electrode slurry. For example, the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry. Then, the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0405] [Negative electrode]
[0406] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on the negative electrode current collector.
[0407] The negative electrode current collector may be a metal foil or a composite negative electrode current collector. The negative electrode current collector may be a copper foil. The composite negative electrode current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0408] The negative electrode film layer includes a negative electrode active material. The negative electrode active material can be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0409] In some embodiments, the negative electrode active material includes a silicon-based material and a carbon-based material, wherein the carbon-based material has a second coating layer. For example, the carbon-based material includes a core portion and a second coating layer disposed on at least a portion of the surface of the core portion, the material of the core portion may be graphite, and the material of the second coating layer may be amorphous carbon.
[0410] As an example, the carbon-based material can be obtained by the following preparation method.
[0411] Providing graphite; fusing the graphite with a coating agent; and carbonizing the fused product under a protective gas atmosphere so that the coating agent is carbonized into a coating layer at least coating the surface of the graphite to obtain a carbon-based material. The carbon-based material includes a core portion and a second coating layer at least partially coating the surface of the core portion, wherein the core portion includes graphite.
[0412] In some embodiments, the carbonization temperature is 700° C. to 1800° C. For example, the carbonization temperature is 700° C., 800° C., 900° C., 1000° C., 1200° C., 1300° C., 1400° C., 1500° C., 1600° C., 1700° C., 1800° C., or any range thereof.
[0413] In some embodiments, the carbonization treatment time is 1 hour to 6 hours. For example, the carbonization treatment time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, or any range thereof.
[0414] In some embodiments, the coating agent includes a liquid coating agent, a solid coating agent, etc. The liquid coating agent may include a liquid soft carbon coating agent, such as liquid asphalt, liquid tar, and other petroleum or coal byproducts. The liquid coating agent may also include a liquid hard carbon coating agent, such as a liquid resin.
[0415] In some embodiments, the solid content of the liquid resin may be 50%-88%, and optionally 60%-85%.
[0416] The solid content of the liquid phase hard carbon coating agent can be tested by the drying method in accordance with GB / T 14074-2017. The free components and water in the liquid phase hard carbon coating agent will volatilize at high temperatures. The solid content of the liquid phase hard carbon coating agent refers to the percentage of the remaining mass to the total mass after drying under specified conditions. The oven temperature is set to 150°C and baked to constant weight.
[0417] When the solid content of the liquid resin is within the above range, the liquid resin can have good fluidity and diffusivity, as well as good curing and coating effects. Thus, the liquid resin can be evenly dispersed on the surface of the graphite particles, thereby making the consistency of the coating layer better and the concentration of the R value of the carbon-based material smaller, thereby better improving the cycle performance of the battery cell.
[0418] In some embodiments, the liquid resin may include at least one of liquid phenolic resin, liquid epoxy resin, liquid vinyl ester resin, liquid unsaturated polyester resin, liquid furan resin, and their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or atomic groups in a polymer by other atoms or atomic groups.
[0419] In some embodiments, the liquid hard carbon coating agent includes liquid phenolic resin, the weight average molecular weight of the liquid phenolic resin can be 300-900, the solid content can be 60%-85%, the mass content of free phenol can be less than or equal to 9%, and the mass content of free aldehyde can be less than or equal to 0.5%.
[0420] Optionally, the weight average molecular weight of the liquid phenolic resin may be 500-700, the solid content may be 70%-78%, the mass content of free phenol may be less than or equal to 6.5%, and the mass content of free aldehyde may be less than or equal to 0.2%.
[0421] Optionally, the weight average molecular weight of the liquid phenolic resin may be 500-700, the solid content may be 70%-78%, the mass content of free phenol may be less than or equal to 6.5%, and the mass content of free aldehyde may be 0.
[0422] The weight average molecular weight of the liquid phenolic resin can be tested by gel permeation chromatography. The testing instrument can be an Agilent 1290 Infinity II GPC system. The eluent can be tetrahydrofuran, and polystyrene standards are used for calibration.
[0423] The content of free phenol in liquid phenolic resin can be tested with reference to GB / T 30773-2014.
[0424] The free aldehyde content in liquid phenolic resin can be tested by potentiometric titration according to GB / T 32684-2016.
[0425] Compared with other liquid resins, the hard carbon formed by the carbonization and coking of liquid phenolic resin itself has better performance, which can make the concentration of the R value of carbon-based materials smaller, and thus better improve the cycle performance of battery cells.
[0426] The weight average molecular weight of the liquid phenolic resin is within the above range, which can make the liquid phenolic resin have good fluidity and diffusivity, as well as good curing effect and coating effect. Therefore, the liquid phenolic resin can be evenly dispersed on the surface of the graphite particles, so as to make the consistency of the coating layer better and the concentration of the R value of the carbon-based material smaller, thereby better improving the kinetic performance of the negative electrode active material and the battery.
[0427] Free phenol is a small molecule, which can easily escape during the carbonization process and form local defects on the surface of the coating layer.
[0428] The mass content of free phenol in the liquid phenolic resin is within the above range, which can reduce the escape of free phenol during the carbonization treatment, reduce local defects on the surface of the coating layer, and reduce the specific surface area of the carbon-based material. This can improve the consistency of the coating layer, the particle consistency of the carbon-based material, and the concentration of the R value of the carbon-based material, thereby better improving the cycle performance of the battery cell.
[0429] The liquid phenolic resin can be a phenolic compound, an aldehyde compound, etc., which is formed by condensation in the presence of an alkaline catalyst. The condensation reaction begins to generate a liquid. The liquid phenolic resin mentioned in the embodiment of the present application is a resol phenolic resin.
[0430] The phenolic compound may include one or more of phenol, cresol, dimethylphenol, nonylphenol, bisphenol A, bisphenol F, resorcinol, propylphenol, ethylphenol, and cardanol, and phenol may be selected. The aldehyde compound may include one or more of formaldehyde, acetaldehyde, butyraldehyde, paraformaldehyde, and furfural, and formaldehyde may be selected. The alkali catalyst may include one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia, sodium carbonate, and tertiary amine.
[0431] In some embodiments, the coking value of the liquid phase hard carbon coating agent may be 35%-50%, and optionally 38%-48%.
[0432] The coking value of the liquid hard carbon coating agent is within the above range, and a larger amount of liquid hard carbon coating agent can be used for solid-liquid fusion, thereby making the liquid hard carbon coating agent evenly dispersed on the surface of the graphite particles, thereby making the consistency of the coating layer better and the R value of the carbon-based material less concentrated, thereby improving the cycle performance of the battery cell.
[0433] The coking value of the liquid phase hard carbon coating agent refers to the percentage of the residual carbon mass left after a quantitative liquid phase hard carbon coating agent sample is heated under specified conditions to the mass of the liquid phase hard carbon coating agent sample, and can be tested with reference to GB / T8727-2008.
[0434] In some embodiments, the mass of the liquid-phase hard carbon coating agent can be 1%-10% of the mass of the graphite, for example, 1%, 1.8%, 2.5%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range of any of the above values. Optionally, the mass of the liquid-phase hard carbon coating agent can be 3.5%-7% of the mass of the graphite.
[0435] As the mass proportion of the liquid-phase hard carbon coating agent increases, the R value R50 of the cumulative distribution of the carbon-based material increases, and the disorder of the surface of the carbon-based material particles increases.
[0436] When the mass proportion of the liquid phase hard carbon coating agent is within the above range, more surfaces of the core can be coated, thereby improving the consistency of the coating, which is beneficial for the battery to have a long cycle life.
[0437] In some embodiments, the device for solid-liquid fusion of graphite and liquid hard carbon coating agent may be a fusion machine.
[0438] Optionally, the stirring speed of the fusion machine can be 300r / min-1000r / min, for example, it can be 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min, 650r / min, 700r / min, 750r / min, 800r / min, 850r / min, 900r / min, 1000r / min, or a range consisting of any of the above numerical values.
[0439] As the stirring speed of the fusion machine increases, the distribution uniformity of the liquid hard carbon coating agent on the surface of the graphite particles is improved, and the consistency of the coating layer is improved; however, too fast a stirring speed may break the structure of the graphite and may also cause the loss of the liquid hard carbon coating agent. For example, part of the liquid hard carbon coating agent may adhere to the inner wall of the fusion machine.
[0440] Optionally, the stirring time for solid-liquid fusion can be 3 min-8 min, for example, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, or a range consisting of any of the above values.
[0441] As the stirring time of solid-liquid fusion increases, the distribution uniformity of the liquid hard carbon coating agent on the surface of the graphite particles is improved, and the consistency of the coating layer is improved; however, if the stirring time is too long, the improvement effect is not obvious and energy consumption will also increase.
[0442] In some embodiments, the method for providing graphite includes the following steps: providing coke raw material; crushing, shaping and grading the coke raw material to obtain aggregate; mixing the obtained aggregate with a binder and sequentially granulating and graphitizing to obtain graphite.
[0443] The particle size of the coke raw material is usually relatively large, and the particle size of the coke raw material can be reduced by crushing. Optionally, the crushing process can include two steps: coarse crushing and pulverizing. Coarse crushing can crush the coke raw material into millimeter-level block particles. Pulverizing can crush the particle size of the particles from the millimeter level to tens of micrometers. After the crushing process, the surface of the coke raw material is uneven, and the shaping process can make the coke raw material particles themselves more rounded. The grading process can reduce the content of particles with too large and too small particle sizes, and can further adjust the particle size and particle size distribution of the coke raw material.
[0444] The coke raw material may include one or more of petroleum-based needle coke and coal-based needle coke.
[0445] Alternatively, the binder may include asphalt.
[0446] The equipment used for the granulation process may include either a horizontal reactor or a vertical reactor.
[0447] Optionally, the granulation process can adopt a step-wise heating and heat preservation process, thereby making the graphite have good secondary particle morphology and high capacity.
[0448] Optionally, the temperature of the graphitization treatment can be 2800℃-3800℃, for example, it can be 2800℃, 2850℃, 2900℃, 3000℃, 3100℃, 3200℃, 3300℃, 3400℃, 3500℃, 3600℃, 3700℃, 3800℃, or a range consisting of any of the above values.
[0449] Optionally, the graphitization treatment time is 10 to 15 days, for example, 10 days, 11 days, 12 days, 13 days, 14 days, 15 days or any range thereof.
[0450] The graphitization temperature is high, the graphitization treatment time is long, the specific capacity of graphite is high, the disorder degree is small, and the cumulative distribution of graphite is 50% and the R value R50 is small.
[0451] The negative electrode film layer may also optionally include a binder. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0452] The negative electrode film layer may also optionally include a conductive agent, which may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0453] In one embodiment, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet are formed into a negative electrode slurry. For example, the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry. Then, the negative electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0454] [Isolator]
[0455] The separator is used to separate the positive electrode sheet from the negative electrode sheet. The present application has no particular limitation on the type of separator, for example, any known porous structure separator with good chemical stability and mechanical stability can be selected.
[0456] In one embodiment, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0457] [Method for preparing lithium-ion battery monomer]
[0458] Figure 3 A method for preparing a lithium-ion battery cell according to an embodiment of the present application. Figure 3 As shown, the method 200 for preparing a lithium-ion battery cell includes step 210 and step 220 .
[0459] Step 210 includes: providing a positive electrode sheet, and placing the positive electrode sheet into a housing.
[0460] In step 210, the positive electrode sheet, the negative electrode sheet, and the separator may be assembled into an electrode assembly, and then the electrode assembly may be placed in a housing. The housing is provided with a pressure relief mechanism, and the actuation pressure P of the pressure relief mechanism satisfies: 0.5MPa≤P≤1.8Mpa.
[0461] The positive electrode plate includes a positive electrode film layer, the positive electrode film layer includes a positive electrode active material, and the positive electrode active material includes a lithium transition metal oxide.
[0462] Step 220 includes: providing an electrolyte, and injecting the electrolyte into the housing to obtain a lithium-ion battery cell.
[0463] As an example, after the electrolyte is injected into the shell, a lithium-ion battery cell can be obtained after standing, forming, aging and other processes.
[0464] The electrolyte includes a carboxylic acid ester solvent and a first additive, and the reduction decomposition potential V1 of the first additive satisfies: 1.45V <V1≤2V。
[0465] In some embodiments, the first additive includes one or more of LiDFOP, 3DTD, or LiDFOB.
[0466] In some embodiments, the electrolyte further includes a second additive, and a reduction decomposition potential V2 of the second additive satisfies: 1.0V≤V1≤1.45V.
[0467] In some embodiments, the second additive includes one or more of MMDS, FEC, VC, or PS.
[0468] In some embodiments, the ionic conductivity of the electrolyte is 9 mS / cm to 23 mS / cm, and / or the viscosity of the electrolyte is 1 mm 2 / s~3mm 2 / s.
[0469] In some embodiments, based on the total mass of the electrolyte, the mass content W3 of the carboxylate solvent satisfies: 5wt%≤W3≤80wt%.
[0470] W3 may be 5wt%, 10wt%, 15wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or any value within the above range.
[0471] When W3 is greater than or equal to 5wt%, the electrolyte has a lower viscosity, a higher ionic conductivity, and the lithium-ion battery cell has a better fast charging performance; when W3 is less than or equal to 80wt%, the consumption of active lithium ions and gas production can be reduced, which is beneficial to improving the cycle life and reliability of the lithium-ion battery cell.
[0472] It should be understood that in the embodiment of the preparation method of the lithium-ion battery monomer, the explanation of the first additive, the second additive, and the carboxylic acid ester solvent can be referred to the embodiment of the electrolyte part and the embodiment of the lithium-ion battery monomer part, and will not be repeated here. In addition, in the embodiment of the preparation method of the lithium-ion battery monomer, the mass content of the first additive, the second additive, and the carboxylic acid ester solvent is the mass content before formation, that is, the mass content when feeding.
[0473] [Lithium-ion battery]
[0474] An embodiment of the present application provides a lithium-ion battery, including the lithium-ion battery cell in the above embodiment. Figure 4 Schematic diagram of a lithium-ion battery according to an embodiment of the present application, wherein the lithium-ion battery cells 3 can directly form a lithium-ion battery 5, or can first form a battery module, and then multiple battery modules form a lithium-ion battery 5.
[0475] In some embodiments, the lithium-ion battery 5 may include a plurality of lithium-ion battery cells 3 .
[0476] [Electrical devices]
[0477] An embodiment of the present application provides an electrical device, comprising the lithium-ion battery described in the above embodiment.
[0478] Figure 5 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application. Figure 5As shown, the present application provides an electric device, which may be a vehicle 6 , and includes the lithium-ion battery 5 in the above embodiment.
[0479] Optionally, the electrical device may also be an energy storage device, a lighting device, a spacecraft, etc. The embodiments of the present application include but are not limited to these.
[0480] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0481] [Example]
[0482] Example 1
[0483] In Example 1, the positive electrode active material, negative electrode active material and electrolyte used to prepare the lithium-ion battery cell are as follows.
[0484] The positive electrode active material is LiNi 0.65 Co 0.07 Mn 0.28 The non-agglomerated primary particles (i.e., the positive electrode active material is a single crystal material), the mass ratio of the cobalt element near the surface of the positive electrode active material particle and the mass ratio of the cobalt element near the center of the positive electrode active material particle is 1.1, and the surface of the positive electrode active material has a coating layer, and the coating layer includes Li3V(MoO4)3 and TiO2;
[0485] The negative electrode active material includes a carbon-based material and a silicon-based material, the carbon-based material includes a core portion and a second coating layer on at least part of the surface of the core portion, the material of the second coating layer is amorphous carbon, the material of the core portion is artificial graphite, the R50 of the carbon-based material is 0.3, the air oxidation temperature T0 is 730° C., the silicon-based material is a silicon-carbon composite, based on the total mass of the negative electrode active material, the mass content of the carbon-based material is 97wt%, the mass content of the silicon-carbon composite is 3wt%, and the concentration of the R value of the carbon-based material is (R90-R10) / R50 is 2.2;
[0486] The solvent in the electrolyte includes methyl acetate MA, ethylene carbonate EC and dimethyl carbonate DMC in a mass ratio of 2:3:5. The electrolyte salt in the electrolyte is LiPF6, and the concentration of the electrolyte salt is 1.1 mol / L. The first additive in the electrolyte is 3DTD. Based on the total mass of the electrolyte, the mass content of the first additive before formation is 1wt%. The second additive in the electrolyte is FEC. Based on the total mass of the electrolyte, the mass content of the second additive before formation is 1wt%.
[0487] The material of the shell and the end cover of the lithium-ion battery cell includes aluminum, and the actuation pressure of the pressure relief mechanism is 0.6 MPa.
[0488] Example 2
[0489] The difference between Example 2 and Example 1 is that the mass content and type of the first additive and the second additive are different.
[0490] Example 3
[0491] The difference between Example 3 and Example 1 is that the mass content and type of the first additive and the second additive are different.
[0492] Example 4
[0493] The difference between Example 4 and Example 1 is that only the first additive is added without adding the second additive, and the first additive is 3DTD.
[0494] Example 5
[0495] The difference between Example 5 and Example 1 is that only the first additive is added without adding the second additive, and the first additive is LiDFOP.
[0496] Example 6
[0497] The difference between Example 6 and Example 2 is that LiDFOB is not added.
[0498] Example 7
[0499] The difference between Example 7 and Example 2 is that FEC is replaced by VC.
[0500] Example 8
[0501] The difference between Example 8 and Example 2 is that the R50 of the carbon-based material and the air oxidation temperature are different. It should be noted that when the R50 of the carbon-based material changes, the air oxidation temperature of the carbon-based material will also change.
[0502] Example 9
[0503] The difference between Example 9 and Example 2 is that the mass proportion of the cobalt element near the surface of the positive electrode active material particle is different from the mass proportion of the cobalt element near the center of the positive electrode active material particle.
[0504] Example 10
[0505] The difference between Example 10 and Example 2 is that the concentration of R values of the carbon-based material (R90-R10) / R50 is different. When the concentration of R values changes, the non-coating rate of the carbon-based material changes.
[0506] Examples 11-12
[0507] The difference between Examples 11-12 and Example 1 is that the actuating pressure of the pressure relief mechanism is different.
[0508] Comparative Example 1
[0509] The difference between Comparative Example 1 and Example 1 is that only the second additive is added without the first additive, the second additive is FEC, and the mass content of FEC is 0.5% based on the total mass of the electrolyte.
[0510] Comparative Example 2
[0511] The difference between Comparative Example 2 and Example 1 is that only the second additive is added without the first additive, the second additive is MMDS, and the mass content of MMDS is 1% based on the total mass of the electrolyte.
[0512] Comparative Example 3
[0513] The difference between Comparative Example 3 and Example 2 is that the actuating pressure of the pressure relief mechanism is different.
[0514] In Examples 1-12 and Comparative Examples 1-3, the single-side density of the positive electrode sheet after formation is 0.11 mg / mm 2 , compacted density is 3.3g / cm 3 ; The surface density of the negative electrode is 0.065mg / mm 2 , compacted density is 1.45g / cm 3 .
[0515] [Preparation of lithium-ion battery monomers]
[0516] (1) Preparation of positive electrode sheet: The positive electrode active material, binder polyvinylidene fluoride (PVDF), and conductive agent (acetylene black) are mixed uniformly in a mass ratio of 96.9:1.1:2, dissolved in solvent N-methylpyrrolidone (NMP), and fully stirred and mixed to prepare a positive electrode slurry, wherein the solid content of the positive electrode slurry is 67%; the positive electrode slurry is uniformly coated on both sides of the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut to obtain a positive electrode sheet; wherein the thickness of the aluminum foil is 13 μm, and the single-side coating weight is approximately 0.11 mg / mm 2 .
[0517] (2) Preparation of negative electrode sheet: artificial graphite, silicon-carbon composite material, thickener sodium carboxymethyl cellulose (CMC-Na), binder styrene-butadiene rubber (SBR), and conductive agent Super-P are dissolved in deionized water at a mass ratio of 93.9:3:1.1:1.5:0.5, and the mixture is stirred and mixed to prepare a negative electrode slurry; the negative electrode slurry is coated on both sides of the negative electrode current collector copper foil, and then dried, cold pressed, and cut to obtain a negative electrode sheet; wherein the thickness of the copper foil is 4.5 μm, and the coating weight on one side is about 0.065 mg / mm 2 .
[0518] (3) Isolation film: A polyethylene film with a thickness of 13 μm is used.
[0519] (4) Preparation of electrolyte: The specific formula of the electrolyte is shown in Table 1.
[0520] (5) Preparation of lithium-ion batteries: The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in a shell, and the prepared electrolyte is added. After packaging, standing, forming, aging, and other processes, a lithium-ion battery cell is obtained.
[0521] Table 1 shows the relevant parameters of the electrolytes of Examples 1-7 and Comparative Examples 1-2, and Table 2 shows the relevant test results of Examples 1-7 and Comparative Examples 1-2. It should be noted that the relevant parameters of the electrolytes in Table 1 are the parameters of the electrolytes added during the preparation of the lithium-ion battery monomers, that is, the relevant parameters of the electrolytes before formation, and the relevant parameters of the electrolytes in Table 2 are the relevant parameters after formation.
[0522] Table 1 Related parameters of electrolytes of Examples 1-7 and Comparative Examples 1-2
[0523]
[0524] Table 2 Related test results of Examples 1-7 and Comparative Examples 1-2
[0525]
[0526] In the embodiment of the present application, the fast charging performance of the lithium-ion battery cell is reflected by the charging time from 10% SOC to 80% SOC. The shorter the charging time, the better the fast charging performance; the cycle life of the lithium-ion battery cell is reflected by the number of cycles when the battery cell cycles to 80% SOH. The more cycles, the longer the cycle life. In addition, since there is currently no particularly clear means to measure the SEI film and CEI film, the quality of the SEI film and CEI film is indirectly fed back through the cycle life and fast charging performance data.
[0527] As shown in Examples 1-7 and Comparative Examples 1-2, when the positive electrode active material includes a transition metal oxide of lithium and the electrolyte includes a carboxylic acid ester solvent, by adding a first additive to the electrolyte, and the reduction decomposition potential of the first additive is greater than 1.45V and less than or equal to 2V, it is beneficial to improve the cycle life of the lithium-ion battery cell while taking into account the fast charging performance of the lithium-ion battery cell.
[0528] As shown in Examples 1-3 and Examples 4-5, compared with adding only the first additive, adding the first additive and the second additive to the electrolyte helps to further improve the cycle life of the lithium-ion battery cell.
[0529] As shown in Examples 1-3, when the total mass content of the first additive and the second additive is greater than or equal to 2wt%, compared with Comparative Examples 1 and 2, the cycle life of the lithium-ion battery cell is significantly improved, and the lithium-ion battery cell still has excellent fast charging performance.
[0530] As shown in Examples 1-3, when the total mass content of the first additive and the second additive does not exceed about 10wt%, the lithium-ion battery cell has a longer cycle life and better fast charging performance.
[0531] As shown in Examples 1-3, the total mass content of the first additive and the second additive is set in the range of 2wt% to 10wt%, and the lithium-ion battery cell has a higher cycle life and better fast charging performance.
[0532] As shown in Examples 2 and 6, the use of 3DTD and LiDFOP in combination with LiDFOB is beneficial to further improve the cycle life of the battery cell.
[0533] As shown in Examples 2 and 7, compared with VC, FEC is more conducive to improving the cycle life and fast charging performance of lithium-ion battery cells.
[0534] Table 3 shows the test results of Example 2 and Examples 8-10. In Table 3, T0 represents the air oxidation temperature of the carbon-based material, P1 represents the mass ratio of the cobalt element near the surface of the positive electrode active material particle and the mass ratio of the cobalt element near the center of the positive electrode active material particle, and the uncoated ratio is the number ratio of the R value less than or equal to 0.11 in the R value of the obtained carbon-based material.
[0535] Table 3 Test results of Example 2 and Examples 8-10
[0536]
[0537] As shown in Table 3, R50, air oxidation temperature T0, concentration (R90-R10) / R50, uncoated rate, and the mass proportion of cobalt element near the surface of the positive electrode active material particles and the mass proportion of cobalt element near the center of the positive electrode active material particles P1 of the carbon-based material are related to the cycle life of the lithium-ion battery cell.
[0538] The smaller R50 is and the higher T0 is within a certain range, the better it is to improve the cycle life of lithium-ion battery cells; the smaller the concentration of R value (R90-R10) / R50 is, the lower the non-coverage rate is, which is beneficial to improve the cycle life of lithium-ion battery cells; within a certain range, the higher P1 is, the better it is to improve the cycle life of lithium-ion battery cells.
[0539] By setting R50 to 0.15-0.50, the lithium-ion battery monomer has a longer cycle life; by setting T0 to 630°C-730°C, the lithium-ion battery monomer has a longer cycle life; by setting the concentration of R value (R90-R10) / R50 to be less than or equal to 2.3, the lithium-ion battery monomer has a longer cycle life; by setting the uncoated rate of carbon-based materials to be less than or equal to 7%, the lithium-ion battery monomer has a longer cycle life; by setting P1 to 1.01-5, the lithium-ion battery monomer has a longer cycle life.
[0540] Table 4 shows the test results of Example 2, Example 5, Examples 11-12 and Comparative Example 3. In Table 4, P represents the actuation pressure of the pressure relief mechanism, and D represents the storage days of the lithium-ion battery cell.
[0541] Table 4 Test results of Example 2, Example 5, Examples 11-12 and Comparative Example 3
[0542] P(MPa) D (day) Example 2 0.6 160 Example 5 0.5 85 Embodiment 11 0.5 120 Example 12 1.8 380 Comparative Example 3 0.3 20
[0543] As shown in Example 2, Example 5, Examples 11-12 and Comparative Example 3, setting the actuation pressure of the pressure relief mechanism within the range of 0.5MPa to 1.8MPa is beneficial to improving the storage life of the lithium-ion battery cell. When the actuation pressure of the pressure relief mechanism exceeds 1.8MPa, when the battery cell is actuated, the risk of the emission being discharged from locations other than the pressure relief mechanism (such as the housing) increases, and the risk of the housing exploding and cracking increases, which is not conducive to improving the reliability of the battery cell.
[0544] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
[0545] The following is a brief introduction to the test methods of the physical and chemical parameters and performance parameters involved in the embodiments of the present application. It should be understood that the following test methods are only examples, and other test methods known in the art may also be used for testing.
[0546] 1. Test method for reduction decomposition potential of additives
[0547] 1 wt% of additives are added to a blank electrolyte, the blank electrolyte only contains a non-aqueous solvent (for example, the solvent is EC, EMC in a mass ratio of 3:7) and a lithium salt LiPF6, and they are mixed evenly; a lithium sheet is used as the negative electrode and a graphite electrode is used as the positive electrode to assemble into a button battery; the battery is left to stand and activated for 2 hours at 45°C on a constant current charge and discharge test instrument, and then discharged to 5 mV at 200uA first, then discharged to 5 mV at 50uA, left to stand for 5 minutes, and charged to 2V at a constant current of 0.1C current, and the test results are presented as a dQ / dV-V graph, wherein Q represents the discharge capacity of the battery, V represents the voltage, and dQ / dV represents the differential of the discharge capacity of the battery with respect to the voltage; the peak position corresponding to the additive can be identified according to the above graph, thereby obtaining the reduction potential of the additive.
[0548] It should be noted that the battery cell may be disassembled first to obtain the electrolyte, and after confirming the specific type of the additive in the electrolyte, the reduction decomposition potential of the additive may be tested according to the above method.
[0549] 2. Test methods for the types and mass contents of the first and second additives
[0550] The masses of the first additive and the second additive can be measured by gas chromatography, gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), and inductively coupled plasma optical emission spectroscopy (ICP-OES).
[0551] The mass content of the first additive in the electrolyte refers to: the mass of the first additive divided by the mass of the entire electrolyte; the mass content of the second additive in the electrolyte refers to: the mass of the second additive divided by the mass of the entire electrolyte.
[0552] As an example, the test is performed by nuclear magnetic resonance spectroscopy, and the specific process is as follows: 500 μl of deuterated reagent is added to the nuclear magnetic tube in a glove box filled with nitrogen, 100 μl of non-aqueous electrolyte sample is added to the nuclear magnetic tube, the nuclear magnetic tube is shaken to dissolve the non-aqueous electrolyte into the deuterated reagent, and the desktop nuclear magnetic resonance spectrometer X-Pulse of Oxford Instruments is used to test the electrolyte composition and quality.
[0553] 3. Testing method of carbon nanotubes in positive electrode film
[0554] The positive electrode sheet was observed using a scanning electron microscope (SEM) to observe the shape of particles in the positive electrode film layer. Among them, the linear particles are carbon nanotubes.
[0555] 4. Test method for actuation pressure of pressure relief mechanism
[0556] Use two plates to clamp the two large faces of the lithium-ion battery cell, and clamp the large faces of the battery cell from both sides (the distance between the two plates is equal to the distance between the two large faces of the battery cell), and inflate the battery cell until the pressure relief mechanism is actuated, at which point the battery cell fails, and record the pressure in the housing of the battery cell (i.e., the actuation pressure of the pressure relief mechanism). When the pressure relief mechanism is actuated, the bulging distance of the two plates is less than or equal to 3 mm (the bulging distance refers to the maximum distance of the plate protrusion, i.e., the distance that any part of the plate moves from the position when clamped to the position after bulging).
[0557] 5. Test method for ionic conductivity of electrolyte
[0558] The test method is in accordance with HG / T 4067-2015. The ionic conductivity of the electrolyte to be tested is tested with a conductivity meter: about 100 ml of the sample to be tested is taken from a dry, clean, corrosion-resistant sample bottle, and sealed in a constant temperature water bath at 25±0.5℃. When the temperature of the sample to be tested is constant, the sample bottle cap is replaced with a rubber stopper with an electrode inserted. When the temperature is within the range of 25±0.5℃, the data is read, which is the ionic conductivity of the sample to be tested.
[0559] 6. Test method for electrolyte viscosity
[0560] The viscosity of the electrolyte can be measured using instruments and methods known in the art. For example, non-Newtonian fluids can refer to the rotational viscometer method provided in the national standard GB / T22235-2008 "Determination of Liquid Viscosity". Specifically, a certain mass of electrolyte sample is placed in a sample container and tested using a rotational viscometer with the instrument model DV2TLV produced by Brookfield. At a certain temperature, the shear force exerted on the rotor when it rotates continuously at a constant speed in the sample causes the spring to generate torque, which is proportional to the viscosity, and the viscosity value is obtained. The test equipment meets the following test environmental conditions: 1. External environment of the equipment: temperature is 15-28°C, humidity is RH<80%; 2. Internal environment of the equipment: 2 / 3 of the sample container is immersed in a water bath, the medium is water, and water is used to keep the sample at a constant temperature.
[0561] 7. Test methods for carboxylic acid ester solvents
[0562] The content of carboxylic acid ester in the electrolyte was quantitatively analyzed by organic gas chromatography analysis method with reference to standard GB / T9722-2006.
[0563] 8. Charging time test method
[0564] The lithium-ion battery cell is charged and discharged for the first time at a rate of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour), specifically including: at 35°C, the battery is charged at a constant current rate of 1C to a voltage of 4.4V, then charged at a constant voltage to a current ≤0.05C, left to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to a voltage of 2.5V, and its actual capacity is recorded as C0. Then the battery is charged with constant current of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, 3.5C0, 4C0, 4.5C0, 5C0 in sequence to the full battery charge cut-off voltage of 4.4V or 0V negative electrode cut-off potential (whichever is reached first). After each charge is completed, it is necessary to discharge with 1C0 to the discharge cut-off voltage of the battery cell of 2.5V. Record the SOC (State of Charge) at different charge rates to 10%, 20%, 30%, ..., 80% Charge, state of charge, when "SOC = 0" indicates that the battery is fully discharged, when "SOC = 100%" indicates that the battery is fully charged) the corresponding negative electrode potential, draw the negative electrode potential curve of the charging rate under different SOC states, and after linear fitting, obtain the charging rate corresponding to the negative electrode potential of 0V under different SOC states. This charging rate is the charging window under this SOC state, which are recorded as C(10% SOC), C(20% SOC), C(30% SOC), C(40% SOC), C(50% SOC), C(60% SOC), C(70% SOC), C(80% SOC), and the maximum charging rate under the corresponding charge state, that is, the fast charging window, is obtained. The charging time from 10% to 80% SOC is 6 / C (20% SOC) + 6 / C (30% SOC) + 6 / C (40% SOC) + 6 / C (50% SOC) + 6 / C (60% SOC) + 6 / C (70% SOC) + 6 / C (80% SOC).
[0565] 9. Cycle life test method
[0566] At 45°C, the prepared battery was charged at a constant current of 1C to 4.4V, then charged at a constant voltage of 0.05C, left for 30 minutes, and then discharged at a constant current of 1C to 2.5V. The discharge capacity was recorded as C0. The battery was cycled according to the above charge and discharge process, and the number of cycles when the discharge capacity decayed to 80% SOH was recorded.
[0567] 10. Test methods for surface density and compacted density
[0568] The positive and negative pole pieces are removed from the lithium-ion battery cell, and the pole piece thickness and the current collector thickness are measured respectively. The pole pieces are punched into small discs with an area of S1 (if the pole pieces are coated on both sides, the film layer on one side can be wiped off first), and their weight is weighed and recorded as M1. Then, the film layer of the weighed pole pieces is wiped off, and the weight of the current collector is weighed and recorded as M0. The single-side density of the pole piece = (M1-M0) / S1.
[0569] The compaction density of the pole piece = pole piece surface density / (pole piece thickness-current collector thickness).
[0570] 11. Storage life test
[0571] The prepared lithium-ion battery cell was charged to 100% SOC at a rate of 0.1C and stored at 60°C. The internal pressure of the lithium-ion battery cell was monitored online using a barometer. The cut-off pressure was 1 / 2 of the actuation pressure of the pressure relief mechanism. The number of days stored at 60°C was recorded.
[0572] 12. Test of R50
[0573] The R value R50 of the carbon-based material can be obtained by the surface scanning mode of the laser micro-confocal Raman spectrometer. As an example, specifically, a laser micro-confocal Raman spectrometer (such as a high-precision Renishaw laser micro-confocal Raman spectrometer) is used, a laser wavelength of 532nm is selected, and an appropriate amount of sample is taken to perform a full-scale surface scan on its surface, the scanning area is 100μm×100μm, the step length is 2μm, and the total number of scanning points is 2500 points, thereby obtaining the R values of different sites and the cumulative distribution curve of the R value of the surface scanning area.
[0574] 13. Test of air oxidation temperature
[0575] The air oxidation temperature T0 can be determined according to a thermogravimetric analysis comprising the following steps: the negative electrode active material is subjected to a thermogravimetric test under the conditions of a weighing mass of 10±0.05 mg, a purge gas of air and an air flow rate of 60 mL / min, a heating rate of 5°C / min, and a test temperature range of 35°C to 950°C, to obtain a thermogravimetric curve (also called a TG curve) and a differential thermogravimetric curve (also called a DTG curve), the peak top temperature T1 of the maximum area peak is read from the differential thermogravimetric curve, and the intersection of two tangents at two points corresponding to the temperatures of 500°C and T1, respectively, is determined on the thermogravimetric curve, and the temperature corresponding to the intersection on the thermogravimetric curve is the air oxidation temperature T0 of the composite graphite material.
[0576] 14. Test of Co content
[0577] The mass proportion of the cobalt element in the positive electrode active material (e.g., lithium transition metal oxide) particles can be obtained by measuring the mass percentage of the cobalt element relative to all elements at different positions of the cross section of the positive electrode active material particles. As an example, an argon ion cross-section polisher (model JEOL IB-19530CP) and a scanning electron microscope (model Zeiss sigma 300) (configured with an X-ray energy spectrometer (EDS, model Oxford energy spectrometer OXFord X-Max-50mm2)) can be used for measurement. The longitudinal cross section of the positive electrode film layer is obtained by using an ion cross-section polisher, and a scanning electron microscope is used to perform a line scan of the Co element on the cross section of the positive electrode active material particles. The mass proportion of the cobalt element near the particle surface is greater than the mass proportion of the cobalt element near the cross section center of the positive electrode active material particle.
[0578] The ratio of the mass percentage of cobalt element at the particle surface of the positive electrode active material to the mass percentage of cobalt element at the center can be calculated by the mass ratio of cobalt element at different sites in the line scan. Among them, the surface is the area from the surface of the particle to a depth of 200nm in the direction toward the geometric center of the particle, and the core is a spherical area with a diameter of 200nm with the geometric center of the particle cross section as the center.
[0579] 15. Test of Ni content
[0580] An ion cross-section polisher was used to obtain the longitudinal section of the positive electrode film layer, and a scanning electron microscope was used to perform a line scan of the Ni element on the section of the positive electrode active material particles to test the Ni element content.
[0581] 16. Testing of Si
[0582] An ion cross-section polisher was used to obtain a longitudinal cross section of the negative electrode film layer, and a scanning electron microscope was used to perform a line scan of the Si element on the cross section of the negative electrode active material particles to test whether the Si element was contained.
[0583] 17. Test of primary particle size
[0584] Taking the positive electrode active material as an example, the test method for the particle size of the primary particles is described.
[0585] As an example, a lithium-ion battery cell is disassembled to obtain a positive electrode sheet, the positive electrode film layer of the positive electrode sheet is peeled off, the positive electrode film layer is fully washed with acetone, and the powder is filtered and dried. Take 0.05g of the uniformly mixed powder and dissolve it in 40mL of anhydrous ethanol, then add an appropriate amount of dispersant, stir evenly to obtain a suspension, take 2mL of the suspension and 2mL of anhydrous ethanol and mix them for ultrasonic treatment, the ultrasonic power is 480W, the ultrasonic time is 5min, and the uniformly dispersed suspension is obtained. Take an appropriate amount of the middle layer suspension for transmission electron microscopy test to obtain a transmission electron microscope image. Select 5-10 transmission electron microscope images with a number of 50 to 100 particles as the sampling area, and ensure that at least 500 particles are tested. Then, the projection area of each primary particle in each sampling area can be counted by the Avizo3D software image processing software, which is the primary particle cross-sectional area S. When performing primary particle identification, for particles with obvious adhesion, manual identification and software identification can be combined to determine whether the particle is a single primary particle or two secondary particles. The equivalent circle method is used to obtain the equivalent circle diameter of the primary particle, which is the particle size d of the primary particle.
[0586] The negative electrode active material (eg, silicon-based material, carbon-based material) can be tested in the same manner as above.
[0587] 18. Test of the particle size of primary particles in secondary particles
[0588] The average particle size of the primary particles in the secondary particles can be measured by any method known in the art.
[0589] Taking the positive electrode active material as an example, the test method for the average particle size of the primary particles in the secondary particles is described.
[0590] As an example, obtain a cross section in the thickness direction of the positive electrode sheet, and observe particles in any 10 areas of the same size and shape in the same scanning electron microscope image (SEM) at 10kv and 30k magnification. Then subdivide each of the 10 areas into 5 positions, including the four corners and the center, select the mean particle size of any primary particle at each position under this magnification, and average the mean particle size results of the 5 positions including the four corners and the center to obtain the mean particle size of the primary particles in this area, and then average the particle sizes of the primary particles obtained in the 10 areas as the average particle size of the primary particles. Specifically, take the average of the major diameter and minor diameter of each particle as the mean particle size of the particle.
[0591] 19. Volume average particle size test
[0592] The volume distribution particle size Dv50 of the material represents the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to GB / T19077-2016 particle size distribution laser diffraction method. The test instrument can be the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.
Claims
1. A lithium-ion battery cell, characterized in that: include: A positive electrode sheet, the positive electrode sheet comprising a positive electrode film layer, the positive electrode film layer comprising a positive electrode active material, and the positive electrode active material comprising a lithium transition metal oxide; The electrolyte comprises a carboxylic acid ester solvent and a first additive, wherein the reduction decomposition potential V1 of the first additive satisfies: 1.45V <V1≤2V; The shell is used to accommodate the positive electrode plate and the electrolyte, and the shell is provided with a pressure relief mechanism, and the actuation pressure P of the pressure relief mechanism satisfies: 0.5MPa≤P≤1.8MPa.
2. The lithium-ion battery cell according to claim 1, characterized in that: 0.7MPa≤P≤1.5MPa.
3. The lithium-ion battery cell according to claim 2, characterized in that: 0.8MPa≤P≤1.4MPa.
4. The lithium-ion battery cell according to any one of claims 1 to 3, characterized in that: The first additive includes one or more of fluorophosphate, borophosphate or vinyl sulfate.
5. The lithium-ion battery cell according to any one of claims 1 to 4, characterized in that: The first additive includes: one or more of LiDFOP, 3DTD or LiDFOB.
6. The lithium-ion battery cell according to any one of claims 1 to 5, characterized in that: Based on the total mass of the electrolyte, the mass content of the first additive is less than or equal to 7 wt %.
7. The lithium-ion battery cell according to claim 6, characterized in that: Based on the total mass of the electrolyte, the mass content of the first additive is 1 wt % to 5 wt %.
8. The lithium-ion battery cell according to claim 6, characterized in that: Based on the total mass of the electrolyte, the mass content of the first additive is 0wt% to 4%.
9. The lithium-ion battery cell according to claim 6, characterized in that: Based on the total mass of the electrolyte, the mass content of the first additive is 0.01 wt % to 2.5 wt %.
10. The lithium-ion battery cell according to claim 1, characterized in that: The electrolyte further includes a second additive, and a reduction decomposition potential V2 of the second additive satisfies: 1.0V≤V1≤1.45V.
11. The lithium-ion battery cell according to claim 10, characterized in that: The second additive includes one or more of a carbonate compound, a sulfonate compound, a vinyl sulfate compound, or a sultone compound.
12. The lithium-ion battery cell according to claim 10 or 11, characterized in that: The second additive includes one or more of MMDS, FEC, VC, DTD, 2DTD or PS.
13. The lithium-ion battery cell according to claim 12, characterized in that: The second additive includes: one or more of MMDS, FEC or PS.
14. The lithium-ion battery cell according to any one of claims 10 to 13, characterized in that: Based on the total mass of the electrolyte, the mass content of the second additive is less than or equal to 12 wt %.
15. The lithium-ion battery cell according to claim 14, characterized in that: The mass content of the second additive is 2 wt % to 9 wt % based on the total mass of the electrolyte.
16. The lithium-ion battery cell according to claim 14, characterized in that: The mass content of the second additive is 0 wt % to 10 wt % based on the total mass of the electrolyte.
17. The lithium-ion battery cell according to claim 14, characterized in that: Based on the total mass of the electrolyte, the mass content of the second additive is 0.01 wt % to 7 wt %.
18. The lithium-ion battery cell according to any one of claims 10 to 17, characterized in that: Based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is less than or equal to 16 wt %.
19. The lithium-ion battery cell according to claim 18, characterized in that: Based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 3 wt % to 12 wt %.
20. The lithium-ion battery cell according to claim 18, characterized in that: Based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 0 wt % to 14 wt %.
21. The lithium-ion battery cell according to claim 18, characterized in that: Based on the total mass of the electrolyte, the sum of the mass contents of the first additive and the second additive is 0.02 wt % to 10 wt %.
22. The lithium-ion battery cell according to any one of claims 10 to 21, characterized in that: The first additive includes 3DTD, and the second additive includes FEC.
23. The lithium-ion battery cell according to claim 22, characterized in that: Based on the total mass of the electrolyte, the mass content of the first additive is 1 wt % to 2 wt %, and the mass content of the second additive is 1 wt % to 2 wt %.
24. The lithium-ion battery cell according to any one of claims 10 to 21, characterized in that: The first additive includes 3DTD, LiDFOP and LiDFOB, and the second additive includes MMDS, FEC and PS.
25. The lithium-ion battery cell according to claim 24, characterized in that: Based on the total mass of the electrolyte, the mass content of the first additive is 2 wt % to 4 wt %, and the mass content of the second additive is 5 wt % to 7 wt %.
26. The lithium-ion battery cell according to any one of claims 1 to 25, characterized in that: The positive electrode film layer further includes a conductive agent, and the conductive agent includes carbon nanotubes.
27. The lithium-ion battery cell according to claim 26, characterized in that: Based on the total mass of the positive electrode film layer, the mass content A of the carbon nanotubes satisfies: 0.05wt%≤A≤1wt%.
28. The lithium-ion battery cell according to claim 27, characterized in that: 0.05wt%≤A≤0.5wt%.
29. The lithium-ion battery cell according to any one of claims 26 to 28, characterized in that: The conductive agent further comprises carbon black. Based on the total mass of the positive electrode film layer, the mass content B of the carbon black satisfies: 0.1 wt %≤B≤1 wt %.
30. The lithium-ion battery cell according to claim 29, characterized in that: Based on the total mass of the positive electrode film layer, the sum of the mass contents of the carbon black and the carbon nanotubes is 0.05 wt % to 2 wt %.
31. The lithium-ion battery cell according to any one of claims 1 to 30, characterized in that: The carboxylate solvent includes one or more of methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl acrylate or ethyl acrylate.
32. The lithium-ion battery cell according to claim 31, characterized in that: The carboxylate solvent includes: one or more of methyl acetate and ethyl acetate.
33. The lithium-ion battery cell according to any one of claims 1 to 32, characterized in that: The ion conductivity of the electrolyte is 9 mS / cm to 23 mS / cm.
34. The lithium-ion battery cell according to claim 33, characterized in that: The ion conductivity of the electrolyte is 9 mS / cm to 18 mS / cm.
35. The lithium-ion battery cell according to any one of claims 1 to 34, characterized in that: The viscosity of the electrolyte is 1 mm 2 / s~3mm 2 / s.
36. The lithium-ion battery cell according to any one of claims 1 to 35, characterized in that: Based on the total mass of the electrolyte, the mass content W3 of the carboxylic acid ester solvent satisfies: 5wt%≤W3≤80wt%.
37. The lithium-ion battery cell according to any one of claims 1 to 36, characterized in that: The carboxylate solvent includes methyl acetate. Based on the total mass of the electrolyte, the mass content W4 of the methyl acetate satisfies: 5wt%≤W4≤80wt%.
38. The lithium-ion battery cell according to claim 37, characterized in that: 15wt%≤W4≤30wt%.
39. The lithium-ion battery cell according to any one of claims 1 to 35, characterized in that: The carboxylate solvent includes ethyl acetate. Based on the total mass of the electrolyte, the mass content W5 of the ethyl acetate satisfies: 5wt%≤W5≤80wt%.
40. The lithium-ion battery cell according to claim 39, characterized in that: 15wt%≤W5≤50wt%.
41. The lithium-ion battery cell according to any one of claims 1 to 35, characterized in that: The carboxylate solvent includes methyl acetate and ethyl acetate. Based on the total mass of the electrolyte, the mass content of methyl acetate is 5wt% to 80wt%, and the mass content of ethyl acetate is 5wt% to 80wt%.
42. The lithium-ion battery cell according to claim 41, characterized in that: The carboxylate solvent includes methyl acetate and ethyl acetate. Based on the total mass of the electrolyte, the mass content of methyl acetate is 15wt% to 30wt%, and the mass content of ethyl acetate is 25wt% to 50wt%.
43. The lithium-ion battery cell according to any one of claims 1 to 42, characterized in that: The lithium-ion battery cell further includes: a negative electrode plate, wherein the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes one or more of a carbon-based material or a silicon-based material.
44. The lithium-ion battery cell according to claim 43, characterized in that: The negative electrode active material comprises a carbon-based material and a silicon-based material. Based on the total mass of the negative electrode active material, the mass content of silicon in the silicon-based material is 0.5 wt % to 50 wt %.
45. The lithium-ion battery cell according to claim 44, characterized in that: The mass content of silicon in the silicon-based material is 0.5 wt % to 10 wt % based on the total mass of the negative electrode active material.
46. The lithium-ion battery cell according to any one of claims 43 to 45, characterized in that: The carbon-based material comprises a core portion and a second coating layer at least coated on a surface of the core portion, the core portion comprises graphite, and the carbon-based material satisfies at least one of the following conditions: In the R value cumulative distribution curve of the carbon-based material obtained in the surface scanning mode of the laser microscopic confocal Raman spectrometer, the R value R50 at which the cumulative distribution is 50% is 0.15 to 0.50; Among the R values of the obtained carbon-based materials, the number of R values less than or equal to 0.11 accounts for less than or equal to 15%; In the R value cumulative distribution curve obtained by the carbon-based material in the surface scanning mode of the laser micro-confocal Raman spectrometer, the concentration of R value (R90-R10) / R50 is less than or equal to 2.3; Among all R values obtained by the carbon-based material, the number of R values R50 less than 50% of the cumulative distribution of the core portion accounts for less than or equal to 10%.
47. The lithium-ion battery cell according to claim 46, characterized in that: The carbon-based material satisfies at least one of the following conditions: In the R value cumulative distribution curve of the carbon-based material obtained in the surface scanning mode of the laser microscopic confocal Raman spectrometer, the R value R50 at which the cumulative distribution is 50% is 0.15-0.30; Among the R values of the obtained carbon-based materials, the number of R values less than or equal to 0.11 accounts for less than or equal to 10%; In the R value cumulative distribution curve obtained by the carbon-based material in the surface scanning mode of the laser micro-confocal Raman spectrometer, the concentration of R value (R90-R10) / R50 is less than or equal to 1.7; Among all R values obtained by the carbon-based material, the number of R values R50 less than 50% of the cumulative distribution of the core portion accounts for less than or equal to 6%.
48. The lithium-ion battery cell according to claim 46, characterized in that: In the R value cumulative distribution curve of the carbon-based material obtained under the surface scanning mode of the laser micro-confocal Raman spectrometer, the R value R50 with a cumulative distribution of 50% is 0.15-0.
30.
49. The lithium-ion battery cell according to claim 46, characterized in that: Among the R values of the obtained carbon-based materials, the number of R values less than or equal to 0.11 accounts for less than or equal to 6%.
50. The lithium-ion battery cell according to any one of claims 43 to 49, characterized in that: The air oxidation temperature T0 of the carbon-based material is 630°C to 730°C, wherein the air oxidation temperature T0 is the temperature corresponding to the intersection of two tangents at two points corresponding to 500°C and T1 temperatures on the thermogravimetric curve of the carbon-based material, respectively, and the T1 temperature is the peak top temperature of the maximum area peak in the differential thermogravimetric curve of the carbon-based material. The thermogravimetric curve and the differential thermogravimetric curve can be obtained by thermogravimetric analysis under the following conditions: sample mass 10±0.05 mg, purge gas is air and the airflow rate is 60 mL / min, the heating rate is 5°C / min, and the test temperature range is 35°C to 950°C.
51. The lithium-ion battery cell according to any one of claims 43 to 50, characterized in that: The carbon-based material includes secondary particles formed by agglomeration of primary particles, and the volume average particle size of the carbon-based material is 8 μm to 18 μm.
52. The lithium-ion battery cell according to any one of claims 43 to 50, characterized in that: The carbon-based material includes unagglomerated primary particles, and the volume average particle size of the carbon-based material is 5 μm to 13 μm.
53. The lithium-ion battery cell according to any one of claims 46 to 52, characterized in that: The core portion of the carbon-based material includes artificial graphite, and the second coating layer includes amorphous carbon.
54. The lithium-ion battery cell according to any one of claims 43 to 53, characterized in that: The single-side density of the negative electrode sheet is 0.05 mg / mm 2 ~0.11mg / mm 2 , and / or, the compaction density of the negative electrode sheet is 1.2 g / cm 3~ 1.7g / cm 3 .
55. The lithium-ion battery cell according to any one of claims 1 to 54, characterized in that: The lithium transition metal oxide includes lithium nickel cobalt manganese oxide.
56. The lithium-ion battery cell according to any one of claims 1 to 55, characterized in that: The lithium transition metal oxide includes non-agglomerated primary particles.
57. The lithium-ion battery cell according to claim 56, characterized in that: The volume average particle size of the lithium transition metal oxide is 2 μm to 5 μm.
58. The lithium-ion battery cell according to claim 56 or 57, characterized in that: The lithium transition metal oxide satisfies at least one of the following conditions: Based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of cobalt is less than or equal to 20%; Based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of nickel accounts for less than 80%.
59. The lithium-ion battery cell according to claim 58, characterized in that: The lithium transition metal oxide satisfies at least one of the following conditions: Based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of cobalt accounts for 5% to 12%; Based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of nickel accounts for 65% to 70%.
60. The lithium-ion battery cell according to any one of claims 1 to 55, characterized in that: The lithium transition metal oxide includes secondary particles formed by agglomeration of primary particles, and the lithium transition metal oxide satisfies at least one of the following conditions: The volume average particle size of the lithium transition metal oxide is 6 μm to 15 μm; The average particle size of the primary particles in the secondary particles is 0.1 μm to 1.5 μm; Based on the total molar number of transition metals in the lithium transition metal oxide, the molar content of nickel is greater than or equal to 80%.
61. The lithium-ion battery cell according to any one of claims 1 to 60, characterized in that: In the particles of the lithium transition metal oxide, the mass proportion of the cobalt element near the surface of the particle is greater than the mass proportion of the cobalt element near the center of the particle, wherein the area near the surface of the particle is a region from the surface of the particle to a depth of 200 nm in the direction toward the geometric center of the particle, and the area near the center of the particle is a spherical region with a diameter of 200 nm and the geometric center of the cross section of the particle as the center of the circle.
62. The lithium-ion battery cell according to claim 61, characterized in that: The ratio of the mass proportion of the cobalt element near the surface of the particle to the mass proportion of the cobalt element near the center of the particle is 1.01-5.
63. The lithium-ion battery cell according to any one of claims 1 to 62, characterized in that: The lithium transition metal oxide includes a substrate and a first coating layer that covers at least a portion of the surface of the substrate, wherein the first coating layer includes at least one of V, Mo, Ti, Al or O elements.
64. The lithium-ion battery cell according to any one of claims 1 to 63, characterized in that: The positive electrode active material also includes a lithium-containing phosphate.
65. The lithium-ion battery cell according to claim 64, characterized in that: The mass content of the lithium-containing phosphate is 1 wt % to 50 wt % based on the total mass of the positive electrode active material.
66. The lithium-ion battery cell according to claim 65, characterized in that: The mass content of the lithium-containing phosphate is 1 wt % to 5 wt % based on the total mass of the positive electrode active material.
67. A lithium-ion battery cell according to any one of claims 64 to 66, characterized in that: The lithium-containing phosphate includes at least one of lithium iron phosphate, lithium manganese phosphate or lithium manganese iron phosphate.
68. The lithium-ion battery cell according to any one of claims 1 to 67, characterized in that: The single-side density of the positive electrode sheet is 0.09 mg / mm 2 ~0.15mg / mm 2 , and / or, the compaction density of the positive electrode sheet is 2.5g / cm 3~ 3.8g / cm 3 .
69. The lithium-ion battery cell according to any one of claims 1 to 68, characterized in that: The material of the shell includes steel, and the thickness of the shell is 0.1 mm to 0.5 mm.
70. The lithium-ion battery cell according to claim 69, characterized in that: The thickness of the shell is 0.2 mm to 0.3 mm.
71. A lithium-ion battery cell according to any one of claims 1 to 68, characterized in that: The material of the shell includes aluminum, and the thickness of the shell is 0.3 mm to 1.0 mm.
72. The lithium-ion battery cell according to claim 71, characterized in that: The thickness of the shell is 0.5 mm to 0.6 mm.
73. The lithium-ion battery cell according to any one of claims 1 to 72, characterized in that: The electrolyte further includes a carbonate solvent, and the carbonate solvent includes one or more of ethylene carbonate, dimethyl carbonate, propylene carbonate or ethyl methyl carbonate.
74. The lithium-ion battery cell according to any one of claims 1 to 73, characterized in that: The electrolyte solution further includes an electrolyte salt, and the electrolyte salt includes one or more of LiPF6 or LiFSI.
75. The lithium-ion battery cell according to claim 74, characterized in that: The electrolyte salt includes LiPF6 and LiFSI, and the mass content of LiFSI is 2 wt% to 30 wt% based on the total mass of the electrolyte salt.
76. The lithium-ion battery cell according to any one of claims 1 to 75, characterized in that: The time t for charging the lithium-ion battery cell from 10% SOC to 80% SOC satisfies: t≤15min.
77. The lithium-ion battery cell according to claim 76, characterized in that: t≤10min.
78. A lithium ion battery, characterized in that: Comprising a lithium-ion battery cell according to any one of claims 1-77.
79. An electrical device, characterized in that: Comprising a lithium ion battery according to claim 78.
Citation Information
Patent Citations
Lithium secondary battery electrode and lithium secondary battery
CN107910587A
Battery monomer, battery and electric device
CN117895091A
Lithium ion battery and electric device
CN118693353A
Battery cell, battery device, and electric device
CN119133577A
Battery cell, battery device, and electric device
CN119153758A